Polarizing element and method for manufacturing the same
Patent Information
- Application Number
- CN202210113372.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-02-05
- Filing Date
- 2022-01-29
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-01-29
AI Technical Summary
Existing polarizing films are prone to peeling when bent in flexible displays, making it difficult to meet the requirements for high bending resistance.
The substrate, alignment film, and polarizing film are sequentially stacked. The alignment film is formed by curing a compound containing an orientation polymer and a compound with active hydrogen reactive groups. The polarizing film is formed by curing a polymeric liquid crystal compound, a compound with active hydrogen reactive groups, and a dichroic pigment. The alignment film and polarizing film are aligned by friction treatment or light irradiation to control the liquid crystal alignment and enhance the adhesion between the films.
It reduces the peeling of the polarizing film when bent, improves the bending resistance of the polarizing element, and is suitable for flexible displays.
Smart Images

Figure BDA0003495302880000071 
Figure BDA0003495302880000081 
Figure BDA0003495302880000091
Abstract
Description
Technical Field
[0001] This invention relates to polarizing elements, methods for manufacturing said polarizing elements, and flat panel display devices and flexible display materials comprising said polarizing elements. Background Technology
[0002] Polarizing plates are used in image display devices, such as organic electroluminescent (OLED) display devices, after being bonded to image display elements such as liquid crystal cells and OLED display elements. In recent years, with the increasing demand for thinner image display devices, there has also been a demand for further thinning of polarizing plates and polarizing films, which are one of their constituent elements. Various polarizing plates and polarizing films have been proposed to meet this demand. For example, Patent Document 1 discloses an ultra-thin polarizing element in which a polarizing layer formed by aligning a polymeric liquid crystal compound and a dichroic pigment is sandwiched between a light alignment layer on a substrate.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Application Publication No. 2017-102479 Summary of the Invention
[0006] The problem that the invention aims to solve
[0007] It is hoped that ultra-thin polarizing elements can be suitable for use in flexible displays, etc. However, if the bending diameter becomes smaller, the polarizing film or the like may peel off at the bending point, thus requiring polarizing elements with high bending resistance that are more suitable for use in flexible displays.
[0008] The purpose of this invention is to provide a polarization element that is less prone to peeling when bent.
[0009] Methods for solving problems
[0010] The inventors conducted in-depth research to solve the above-mentioned problems, and as a result, completed this invention. That is, this invention includes the following methods.
[0011] [1] A polarization element, which is formed by sequentially stacking a substrate, an alignment film and a polarization film.
[0012] The orientation film is an orientation film formed by curing an orientation film forming composition comprising an orientation polymer (A-1) and a compound having an active hydrogen reactive group (A-2).
[0013] [2] According to the polarizing element described in [1], the polarizing film is a polarizing film formed by curing a polarizing film forming composition comprising a polymeric liquid crystal compound (B-1), a compound having an active hydrogen reactive group (B-2), and a dichroic pigment (B-3).
[0014] [3] According to the polarization element described in [1] or [2], wherein the compound (A-2) also has a group containing active hydrogen.
[0015] [4] According to any one of [1] to [3], the polarization element is wherein the orientation polymer (A-1) is a polymer having a photoreactive group that produces a dimerization reaction.
[0016] [5] According to any one of the polarization elements described in [1] to [4], wherein the orientation polymer (A-1) is a (meth)acrylic polymer.
[0017] [6] According to any one of [1] to [5], the polarization element is wherein the weight-average molecular weight of the oriented polymer (A-1) is 10,000 or more and 1,000,000 or less.
[0018] [7] The polarizing element described in any one of [1] to [6], wherein compound (A-2) is a silane coupling agent.
[0019] [8] The polarizing element described in any one of [1] to [7], wherein the compound (A-2) is a silane coupling agent containing at least one functional group selected from primary amino, secondary amino, hydroxyl and mercapto groups.
[0020] [9] According to any one of [1] to [8], the content of compound (A-2) is more than 1 part by mass and less than 30 parts by mass relative to 100 parts by mass of the oriented polymer (A-1).
[0021]
[10] According to any one of [2] to [9], the polarizing element, wherein the compound (B-2) further has a polymerizable group.
[0022]
[11] According to the polarizing element described in
[10] , wherein the polymerizable group is (meth)acryloyl.
[0023]
[12] According to any one of [2] to
[11] , the polarizing element wherein the compound (B-2) has one or more isocyanate groups and (meth)acryloyl groups.
[0024]
[13] According to any one of [2] to
[12] , the content of compound (B-2) is 0.1 parts by mass or more and 12 parts by mass or less relative to 100 parts by mass of polymeric liquid crystal compound (B-1).
[0025]
[14] The polarizing element described in any one of [2] to
[13] , wherein the dichroic pigment (B-3) comprises the compound shown in formula (I):
[0026] K 1 (-N=NK) 2 ) p -N=NK 3 (I)
[0027] In formula (I),
[0028] K 1 and K 3 The groups can be represented independently as phenyl groups that may have substituents, naphthyl groups that may have substituents, phenyl benzoate groups that may have substituents, or monovalent heterocyclic groups that may have substituents.
[0029] K 2 This indicates that the substituents may be p-phenylene, naphthalene-1,4-diyl, 4,4'-pyromellitic vinylidene (Japanese: 4,4'-stilbenilenyl), or divalent heterocyclic groups.
[0030] p represents an integer from 0 to 4. When p is an integer greater than 2, there are multiple K. 2 They can be the same or different, and the absorption range can be displayed in the visible region by replacing -N=N- bonds with -C=C-, -COO-, -NHCO-, or -N=CH- bonds.
[0031]
[15] The polarizing element described in any one of [2] to
[14] , wherein the polymeric liquid crystal compound (B-1) is a liquid crystal compound exhibiting smectic liquid crystal properties.
[0032]
[16] The polarizing element described in any one of [1] to
[15] , wherein the thickness of the substrate is 1 μm or more and 10 μm or less.
[0033]
[17] The polarizing element according to any one of [1] to
[16] , wherein the surface of the polarizing film opposite to the orientation film includes an outer coating.
[0034]
[18] A manufacturing method is a method for manufacturing a polarizing element formed by sequentially stacking a substrate, an alignment film, and a polarizing film, the manufacturing method comprising:
[0035] (1) A process of forming a coating film comprising an orientation polymer (A-1) and a compound (A-2) having active hydrogen reactive groups on a substrate having polar groups, drying the coating film, thereby causing the active hydrogen reactive groups of the compound (A-2) to react with the polar groups of the substrate to form a bond.
[0036] (2) A process of subjecting the dried coating obtained in step (1) to friction treatment or light irradiation to form an orientation film;
[0037] (3) A step of forming a coating film comprising a polymerizable liquid crystal compound (B-1), a compound having active hydrogen reactive groups (B-2), and a dichroic pigment (B-3) on the alignment film obtained in step (2), and drying the coating film; and
[0038] (4) A process of curing the polymeric liquid crystal compound (B-1) and dichroic pigment (B-3) in the dry coating obtained in step (3) in an oriented state to form a polarizing film.
[0039]
[19] The manufacturing method described in
[18] further includes a step of forming an outer coating on the polarizing film formed in step (4).
[0040]
[20] A flat panel display device comprising a polarizing element described in any one of [1] to
[17] .
[0041]
[21] A flexible display material comprising a polarizing element described in any one of [1] to
[17] .
[0042] Invention Effects
[0043] According to the present invention, a polarizing element that is not prone to peeling when bent can be provided. Detailed Implementation
[0044] The embodiments of the present invention will now be described in detail. It should be noted that the scope of the present invention is not limited to the embodiments described herein, and various modifications can be made without departing from the spirit of the invention.
[0045] The polarizing element of the present invention comprises, in sequence, a substrate, an alignment film, and a polarizing film. In the polarizing element of the present invention, as a configuration that more easily achieves the effects of the present invention, it is preferable that the substrate, the alignment film, and the polarizing film are each formed adjacent to each other. As long as it does not affect the effects of the present invention, the polarizing element of the present invention may be constructed by including other layers in addition to the substrate, the alignment film, and the polarizing film. Examples of other layers include, for instance, an outer coating layer disposed on the polarizing film, and an adhesive layer for bonding to image display elements such as liquid crystal cells and organic EL display elements.
[0046] <Orientation film>
[0047] The polarizing element of the present invention includes an alignment film, which is formed by curing an alignment film forming composition comprising an alignment polymer (A-1) and a compound having an active hydrogen reactive group (A-2). In the present invention, the alignment film has an alignment limiting force that causes the polymeric liquid crystal compound and dichroic pigment forming the polarizing film (described later) to be aligned in a desired direction. By coating the alignment film with a composition comprising a polymeric liquid crystal compound or the like for forming a polarizing film, a polarizing film with excellent alignment precision can be easily obtained.
[0048] The orientation states of liquid crystals, such as horizontal orientation, vertical orientation, mixed orientation, and tilted orientation, can be controlled by utilizing the properties of the alignment film and the polymeric liquid crystal compound. In this invention, any combination of these orientation states can be arbitrarily selected according to the desired orientation state. For example, by using an alignment film formed from a material exhibiting horizontal orientation as an orientation limiting force, the polymeric liquid crystal compound can be horizontally or mixedly oriented; by using an alignment film formed from a material exhibiting vertical orientation, the polymeric liquid crystal compound can be vertically or tilted. It should be noted that the orientation directions, such as horizontal and vertical orientation, refer to the long axis direction of the oriented polymeric liquid crystal compound relative to the polarization film plane. For example, horizontal orientation refers to a state where the long axis direction of the polymeric liquid crystal compound is oriented parallel to the polarization film plane, and vertical orientation refers to a state where the long axis direction of the polymeric liquid crystal compound is oriented perpendicular to the polarization film plane. Here, "parallel to the polarization film plane" means 0° ± 20° relative to the polarization film plane, and "vertical" means 90° ± 20° relative to the polarization film plane.
[0049] In this invention, the alignment film is formed from an alignment film forming composition containing an alignment polymer (A-1). The alignment constraint force of the alignment film can be arbitrarily controlled by factors such as surface state, friction state, and polarized light irradiation conditions, depending on the type of alignment polymer (A-1) contained in the alignment film forming composition. Furthermore, liquid crystal alignment can also be controlled by selecting the surface tension, liquid crystal properties, and other physical properties of the polymerizable liquid crystal compound.
[0050] As an alignment film, it is preferable to be insoluble in the solvent used when forming the polarizing film on the alignment film, and also to have heat resistance for solvent removal and heat treatment during liquid crystal alignment. Examples of alignment films include rubbing alignment films, photoalignment films, and groove alignment films formed from alignment polymers. From the viewpoint of easy control of the alignment direction and the accuracy of the alignment angle during the manufacture of polarizing elements, and excellent quality, in one embodiment of the present invention, the alignment film is preferably a photoalignment film.
[0051] When the orientation film is a friction-oriented film formed from an orientation polymer, examples of orientation polymers (A-1) include polyamides having amide bonds within the molecule, gelatin-like substances, polyimides having imide bonds within the molecule, and their hydrolysates such as polyamic acid, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethylene imide, polystyrene, polyvinylpyrrolidone, polyacrylic acid, and polyacrylates. Hereinafter, the orientation polymer used for friction-oriented films will also be referred to as a "friction-oriented polymer." Polyvinyl alcohol is preferably used as the friction-oriented polymer. Friction-oriented polymers can be used alone or in combination of two or more.
[0052] When the alignment film is a photoalignment film, the alignment polymer (A-1) is typically an alignment polymer with photoreactive groups. Hereinafter, the alignment polymer used for forming the photoalignment film will also be referred to as a "photoalignment polymer." In this specification, a photoreactive group refers to a group that generates liquid crystal alignment capability upon light irradiation. In the polymer forming the photoalignment film, the photoreactive group contributes to imparting liquid crystal alignment capability due to the action of light. Specifically, it refers to a group that induces polymer molecule alignment through light reactions such as dimerization, isomerization, photocrosslinking, or photodecomposition, which are the origin of liquid crystal alignment capability due to light irradiation. The photoalignment polymer may possess one type of photoreactive group or two or more types.
[0053] As a photoreactive group capable of producing the reaction described above, it is preferable to have a group having unsaturated bonds, especially double bonds. Examples include groups having at least one selected from carbon-carbon double bonds (C=C), carbon-nitrogen double bonds (C=N), nitrogen-nitrogen double bonds (N=N), and carbon-oxygen double bonds (C=O).
[0054] Examples of groups having C=C bonds include vinyl, polyene, bis(phenyl)vinyl, stilbene, stilbeneonyl, chalcone, and cinnamoyl groups. Examples of groups having C=N bonds include groups with structures such as aromatic Schiff bases and aromatic hydrazones. Examples of groups having N=N bonds include azophenyl, azonaphthyl, aromatic heterocyclic azo, diazo, formazanyl, and groups with azobenzene oxide as the basic structure. Examples of groups having C=O bonds include benzophenone, coumarin, anthraquinone, and maleimide groups. These groups may have substituents such as alkyl, alkoxy, aryl, allyloxy, cyano, alkoxycarbonyl, hydroxyl, sulfonic acid, and haloalkyl groups. From the viewpoint of excellent orientation and reactivity, photooriented polymers preferably have photoreactive groups that produce dimerization or photocrosslinking reactions, and more preferably have photoreactive groups that produce dimerization reactions.
[0055] A dimerization reaction refers to an addition reaction between two groups caused by light, typically resulting in the formation of a ring structure. The groups that initiate this dimerization reaction are those containing carbon-carbon double bonds (C=C) or carbon-oxygen double bonds (C=O), which dimerize upon light irradiation. Examples include groups with cinnamoyl, chalcone, coumarin, benzophenone, and anthracene structures. Among these, groups with cinnamoyl and chalcone structures are preferred for ease of reactivity control and excellent orientation confinement during photoorientation, with groups with cinnamoyl being more preferred. Furthermore, groups with these structures require less polarized light irradiation for photoorientation and readily produce photoorientation films with excellent thermal and time stability, which is also advantageous.
[0056] The photooriented polymer preferably has a photoreactive group that generates a dimerization reaction at the end of the polymer side chain, more preferably has a group with a cinnamoyl structure or a chalcone structure at the end of the polymer side chain, and even more preferably has a group with a cinnamoyl structure at the end of the polymer side chain. As such a photooriented polymer, examples include polymers having the structure shown in formula (A1') and / or the structure shown in formula (A1") on the side chain (hereinafter collectively referred to as "photooriented polymer (A)").
[0057] [Chemistry 1]
[0058]
[0059] In formulas (A1') and (A1”),
[0060] k represents 0 or 1.
[0061] L 1 It represents a single bond, or -O-.
[0062] L 2 It represents a single bond, -O-, -COO-, -OCO-, -N=N-, -CH=CH-, or -CH2-.
[0063] R 1 R 2 and R 3 Each of the following groups can independently represent a hydrogen atom, a halogen atom, a haloalkyl group, a haloalkoxy group, a cyano group, a nitro group, an alkyl group, an alkoxy group, an aryl group, an allyloxy group, an alkoxycarbonyl group, a carboxyl group, a sulfonic acid group, an amino group, or a hydroxyl group, wherein the carboxyl group and the sulfonic acid group can form a salt with an alkali metal ion.
[0064] R 4 It represents a hydrogen atom, alkyl group, or phenyl group.
[0065] * Indicates the bond end with the polymer backbone.
[0066] In equations (A1') and (A1”), L 2 The manufacture of photooriented polymer (A) becomes easier when the form is any of -O-, -COO-, -OCO-, -N=N-, -C=C-, and -CH2-.
[0067] R in equation (A1') and equation (A1”) 1 R 2 and R 3 Preferably, each is independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms. As R 1 R 2 and R 3 Examples of alkyl groups include methyl, ethyl, and butyl, while examples of alkoxy groups include methoxy, ethoxy, and butoxy.
[0068] The main chain of the photooriented polymer (A) is not particularly limited. The monomer units forming the main chain can be, for example, selected from the monomer units of formula (M-1) or formula (M-2); (meth)acrylamide units of formula (M-3) or formula (M-4); vinyl ether units of formula (M-5) or formula (M-6); methylstyrene units of formula (M-7) or formula (M-8); and vinyl ester units of formula (M-9) or formula (M-10).
[0069] In formulas (M-1) to (M-10), * represents a bonding end to the structure represented by formula (A1') or formula (A1"), or a bonding end to a spacer unit described later. It should be noted that the "main chain of the photo-orientable polymer (A)" as referred to in this specification means the longest molecular chain among the molecular chains possessed by the photo-orientable polymer (A).
[0070] [Chem. 2]
[0071]
[0072] The main chain of the photo-orientable polymer (A) may be a homopolymer formed from one type of monomer unit, or a copolymer formed from two or more types of monomer units. When the main chain of the photo-orientable polymer (A) is a copolymer, it may have any bonding mode of alternating type, block type, random type, or graft type.
[0073] In addition, the structure of the monomer unit forming the main chain of the photo-orientable polymer (A) may also be a silsesquioxane structure including repeating units represented by formulas (M-11) to (M-16). In formulas (M-11) to (M-16), * represents a bonding end to the structure represented by formula (A1') or formula (A1"), or a bonding end to a spacer unit described later.
[0074] [Chem. 3]
[0075]
[0076] In formulas (M-11) to (M-16), R 5 represents an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or is bonded to another silicon atom via an oxygen atom. Examples of the alkyl group having 1 to 6 carbon atoms represented by R 3 include methyl, ethyl, n-propyl, isopropyl, n-butyl and the like, among which methyl and ethyl are preferred. As the alkoxy group having 1 to 6 carbon atoms represented by R 5 examples include methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy and the like, among which methoxy and ethoxy are preferred.
[0077] In formulas (M-13) and (M-14), Ph represents a divalent benzene ring which may have a substituent (such as phenylene). In formula (M-16), Cy includes a divalent cyclohexane ring which may have a substituent (such as cyclohexane-1,4-diyl) and the like.
[0078] n represents an integer of 1 to 4.
[0079] The backbone of the photooriented polymer (A) is preferably formed from structural units shown in any of formulas (M-1) to (M-16), more preferably from structural units shown in any of formulas (M-1) to (M-10), and even more preferably from structural units selected from (meth)acrylate units and (meth)acrylamide units shown in formulas (M-1) to (M-4).
[0080] The monomer structural unit forming the main chain of the photooriented polymer (A), as shown in any of formulas (M-1) to (M-16), can be directly bonded to the group shown in formula (A1') or formula (A1"), or it can be bonded via a linking group that serves as a suitable spacer unit. In the case of bonding via a linking group, examples of linking groups include carbonyloxy groups (ester bonds), oxygen atoms (ether bonds), imide groups, carbonyl imino groups (amide bonds), imino carbonyl imino groups (urethane bonds), divalent aliphatic hydrocarbon groups that may have substituents, divalent aromatic hydrocarbon groups that may have substituents, and divalent groups formed by combining these. Examples of divalent aromatic hydrocarbon groups that may have substituents include... Phenyl, 2-methoxy-1,4-phenylene, 3-methoxy-1,4-phenylene, 2-ethoxy-1,4-phenylene, 3-ethoxy-1,4-phenylene, 2,3,5-trimethoxy-1,4-phenylene, etc. Among these, aliphatic hydrocarbon groups are preferred, and alkyl diesters with 1 to 11 carbon atoms that may have substituents are more preferred. It should be noted that examples of such alkyl diesters include methylene, ethylene, trimethylene, tetramethylene, pentamethylene, hexamethylene, heptamethylene, octamethylene, nonamethylene, decamethylene, and undecamethylene, which can be linear or branched. Furthermore, examples of substituents that may be present in such alkyl diesters include alkoxy groups with 1 to 4 carbon atoms.
[0081] The structure shown in formula (A1') is preferably formed in the form of a structural unit shown in formula (A1-1) (hereinafter sometimes referred to as "structural unit (A1-1)"). In one embodiment of the invention, the photooriented polymer (A) comprises structural unit (A1-1). Alternatively, the structure shown in formula (A1") is preferably formed in the form of a structural unit shown in (A1-2) (hereinafter also referred to as "structural unit (A1-2)"). In one embodiment of the invention, the photooriented polymer (A) comprises structural unit (A1-2).
[0082] [Chemistry 4]
[0083]
[0084] In equations (A1-1) and (A1-2), L 1 L2 R 1 R 2 R 3 R 4 And k are each synonyms of the letters in the formula (A1') or formula (A1”), SP 1 M is an alkyldiyl group that can have 1 to 11 carbon atoms and may have substituents. 1 The structure shown is any one of the structures shown in equations (M-1) to (M-16).
[0085] The photo-oriented polymer (A) may have a carboxyl group in addition to having photoreactive groups, particularly photoreactive groups that produce dimerization reactions. The photo-oriented polymer (A) having photoreactive groups and carboxyl groups may, for example, be a polymer containing structural unit (A1-1). As another embodiment, it may be a polymer that contains, for example, the structure shown in formula (A1'), the structure shown in formula (A1"), or structural unit (A1-1) and / or structural unit (A1-2), and further contains structural unit (A1-3) (hereinafter also referred to as "structural unit (A1-3)").
[0086] [Chemistry 5]
[0087]
[0088] In formula (A1-3), l represents 0 or 1, SP 2 SP indicates an alkyldiyl group with 1 to 11 carbon atoms that can have substituents. 2 Specific examples and SP in equations (A1-1) and (A1-2) 1 The specific examples are the same, M 2 The structure shown is any one of the structures shown in equations (M-1) to (M-16).
[0089] In formula (A1-3), L 3 Indicates a single bond or -O-, L 4 It represents a single bond, -O-, -COO-, -OCO-, -N=N-, -CH=CH-, or -CH2-.
[0090] In equation (A1-3), R 6 and R 7 Each of these can independently represent a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms. As R 6 and R 7 Examples of alkyl groups include methyl, ethyl, and butyl, while examples of alkoxy groups include methoxy, ethoxy, and butoxy.
[0091] When the photo-alignment polymer (A) comprises structural unit (A1-1) or structural units (A1-2) and (A1-3), and the mole fractions of structural units (A1-1), (A1-2), and (A1-3) relative to all structural units forming the photo-alignment polymer (A) are set as p, q, and r respectively (here, p+r is 1 and q+r is 1), it is preferable to satisfy the relationships 0.10 < p, q ≤ 0.90 and 0.10 ≤ r < 0.90. In the photo-alignment polymer comprising structural unit (A1-1), this structural unit (A1-1) can be one type or two or more types. Furthermore, the photo-alignment polymer (A) may also have structural units other than structural units (A1-1), (A1-2), and (A1-3) (hereinafter sometimes referred to as "other structural units"), as long as it does not significantly impair the liquid crystal alignment capability based on light irradiation.
[0092] Photooriented polymer (A) can be manufactured by (co)polymerizing monomers that derive structural units (A1-1) or (A1-2) with monomers that derive structural units (A1-3) and / or other structural units as needed. As a copolymerization method, any method conventionally known in the art can be used, such as chain polymerization (e.g., free radical polymerization, anionic polymerization, and cationic polymerization) or addition polymerization (e.g., coordination polymerization). The polymerization conditions can be appropriately determined based on the type and amount of monomers used to obtain a photooriented polymer (A) with the desired molecular weight.
[0093] In this invention, the molecular weight of the orientation polymer (A-1) is the weight-average molecular weight of polystyrene determined by gel permeation chromatography (GPC), preferably 10,000 or more and 1,000,000 or less, more preferably 15,000 or more, even more preferably 20,000 or more, further preferably 500,000 or less, and even more preferably 250,000 or less. If the weight-average molecular weight of the orientation polymer (A-1) is within the above range, the solvent resistance becomes good, and it is easy to obtain an orientation film that exhibits excellent liquid crystal orientation ability while ensuring high adhesion to the polarization film subsequently formed on the orientation film.
[0094] In this invention, the orientation polymer (A-1) is preferably a photo-oriented polymer, more preferably a photo-oriented polymer (A), and even more preferably a (meth)acrylic polymer (especially a (meth)acrylic photo-oriented polymer (A)). Particularly when the polymeric liquid crystal compound forming the polarizing film is a compound with a (meth)acryloyl group as its polymeric group, if the orientation polymer (A-1) is a (meth)acrylic polymer, it exhibits excellent affinity, and even with a small bending diameter, further improvement in the bend resistance to suppress the peeling of the polarizing film from the orientation film can be expected. It should be noted that, in this specification, polymers in which the proportion of structural units based on (meth)acrylic acid structures, such as (meth)acrylic ester units and (meth)acrylamide units, is the largest among the structural units forming the polymer backbone are collectively referred to as "(meth)acrylic polymers".
[0095] The content of the orientation polymer (A-1) in the orientation film forming composition can be appropriately determined according to the type of orientation polymer used, the desired thickness of the orientation film, etc. There is no particular limitation as long as the amount of orientation polymer (A-1) used can be completely dissolved; however, its content (concentration) relative to the total mass of the orientation film forming composition is preferably 1.0 to 25.0% by mass, more preferably 2.5 to 22.5% by mass. In the orientation film forming composition, the orientation polymer (A-1) can be only one type, or it can be a combination of two or more types. When two or more types are included, their total content is preferably within the above-mentioned range.
[0096] In this invention, the alignment film forming composition comprises an alignment polymer (A-1) and a compound (A-2) having an active hydrogen reactive group (hereinafter also referred to as "compound (A-2)"). The term "active hydrogen reactive group" in this specification refers to a group reactive to groups having active hydrogen, such as carboxyl (-COOH), hydroxyl (-OH), amino (-NH2), and mercapto (-SH). If the alignment film is formed from the alignment film forming composition comprising compound (A-2) having an active hydrogen reactive group, the adhesion between the substrate and the alignment film is easily controlled, and the effect of suppressing peeling that may occur between the substrate and the alignment film when the resulting polarizing element is bent is improved.
[0097] Examples of active hydrogen reactive groups that can be present in compound (A-2) include epoxy, glycidyl, oxazoline, carbodiimide, aziridinyl, imide, alkoxysilyl, isocyanate, thioisocyanate, and maleic anhydride. From the viewpoint of tightness, it is preferable that compound (A-2) has at least one group selected from alkoxysilyl and isocyanate, and more preferably alkoxysilyl.
[0098] Compound (A-2) has one or more active hydrogen reactive groups. When multiple active hydrogen reactive groups are present, these groups may be identical or different.
[0099] Compound (A-2) preferably has a group containing active hydrogen in addition to a group that is reactive with active hydrogen. In this specification, "a group containing active hydrogen" refers to a functional group containing active hydrogen. If compound (A-2) has a group containing active hydrogen, the adhesion between the alignment film and the polarization film can be easily controlled, and the effect of suppressing peeling that may occur between the alignment film and the polarization film when the resulting polarization element is bent can be improved.
[0100] Examples of active hydrogen-containing groups that can be present in compound (A-2) include hydroxyl, carboxyl, amino, mercapto, primary amide, secondary amide, and hydrazide groups. From the viewpoint of reactivity and compatibility, it is preferable that compound (A-2) has at least one group selected from hydroxyl, amino, and mercapto, and preferably has an amino or mercapto group.
[0101] Compound (A-2) has one or more groups containing active hydrogen. When multiple groups containing active hydrogen are present, these groups may be the same or different.
[0102] In one embodiment of the present invention, compound (A-2) is a silane coupling agent. Using a silane coupling agent as compound (A-2) makes it easier to control the adhesion to the substrate and polarizing film, and facilitates the acquisition of polarizing elements with excellent bending resistance. A single silane coupling agent can be used alone, or two or more can be used in combination.
[0103] As silane coupling agents, compounds known in the art can be used. Specifically, examples include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, 3-epoxypropoxypropyltrimethoxysilane, and 3-epoxypropoxypropylmethyldimethoxysilane. 3-chloropropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropyltrimethoxysilane, 3-acryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-epoxypropoxypropyltrimethoxysilane, 3-epoxypropoxypropyltriethoxysilane, 3-epoxypropoxypropyldimethoxymethylsilane, and 3-epoxypropoxypropylethoxydimethylsilane.
[0104] In addition, silane coupling agents can also be silicone oligomer-type silane coupling agents. As silicone oligomer-type silane coupling agents, if silicone oligomers are represented as (monomer) oligomers, examples include copolymers containing mercaptopropyl groups such as 3-mercaptopropyltrimethoxysilane-tetramethoxysilane copolymer, 3-mercaptopropyltrimethoxysilane-tetraethoxysilane copolymer, 3-mercaptopropyltriethoxysilane-tetramethoxysilane copolymer, and 3-mercaptopropyltriethoxysilane-tetraethoxysilane copolymer; and copolymers containing mercaptomethyl groups such as mercaptomethyl trimethoxysilane-tetramethoxysilane copolymer, mercaptomethyltrimethoxysilane-tetraethoxysilane copolymer, mercaptomethyltriethoxysilane-tetramethoxysilane copolymer, and mercaptomethyltriethoxysilane-tetraethoxysilane copolymer. Polymers; copolymers containing 3-epoxypropoxypropyltrimethoxysilane-tetramethoxysilane, 3-epoxypropoxypropyltrimethoxysilane-tetraethoxysilane, 3-epoxypropoxypropyltriethoxysilane-tetramethoxysilane, 3-epoxypropoxypropyltriethoxysilane-tetraethoxysilane, 3-epoxypropoxypropylmethyldimethoxysilane-tetramethoxysilane, 3-epoxypropoxypropylmethyldimethoxysilane-tetraethoxysilane, 3-epoxypropoxypropylmethyldiethoxysilane-tetraethoxysilane, 3-epoxypropoxypropylmethyldiethoxysilane-tetraethoxysilane, etc.; 3-methyl The following copolymers contain methacryloyloxypropyltrimethoxysilane-tetramethoxysilane: 3-methacryloyloxypropyltrimethoxysilane-tetraethoxysilane, 3-methacryloyloxypropyltriethoxysilane-tetramethoxysilane, 3-methacryloyloxypropyltriethoxysilane-tetraethoxysilane, 3-methacryloyloxypropylmethyldimethoxysilane-tetramethoxysilane, 3-methacryloyloxypropylmethyldimethoxysilane-tetraethoxysilane, 3-methacryloyloxypropylmethyldiethoxysilane-tetraethoxysilane, and 3-methacryloyloxypropylmethyldiethoxysilane-tetraethoxysilane. 3-Acryloyloxypropyltrimethoxysilane-tetramethoxysilane copolymer, 3-Acryloyloxypropyltrimethoxysilane-tetraethoxysilane copolymer, 3-Acryloyloxypropyltriethoxysilane-tetramethoxysilane copolymer, 3-Acryloyloxypropyltriethoxysilane-tetraethoxysilane copolymer, 3-Acryloyloxypropylmethyldimethoxysilane-tetramethoxysilane copolymer, 3-Acryloyloxypropylmethyldimethoxysilane-tetraethoxysilane copolymer, 3-Acryloyloxypropylmethyldiethoxysilane-tetramethoxysilane copolymer, 3-Acryloyloxypropylmethyldiethoxysilane-tetraethoxysilane copolymer, and other copolymers containing acryloyloxypropyl groups;Vinyltrimethoxysilane-tetramethoxysilane copolymer, vinyltrimethoxysilane-tetraethoxysilane copolymer, vinyltriethoxysilane-tetramethoxysilane copolymer, vinyltriethoxysilane-tetraethoxysilane copolymer, vinylmethyldimethoxysilane-tetramethoxysilane copolymer, vinylmethyldimethoxysilane-tetraethoxysilane copolymer, vinylmethyldiethoxysilane-tetramethoxysilane copolymer, vinylmethyldiethoxysilane-tetraethoxysilane copolymer, etc., copolymers containing vinyl groups; 3-aminopropyltrimethoxysilane. -Tetramethoxysilane copolymers, 3-aminopropyltrimethoxysilane-tetraethoxysilane copolymers, 3-aminopropyltriethoxysilane-tetramethoxysilane copolymers, 3-aminopropyltriethoxysilane-tetraethoxysilane copolymers, 3-aminopropylmethyldimethoxysilane-tetramethoxysilane copolymers, 3-aminopropylmethyldimethoxysilane-tetraethoxysilane copolymers, 3-aminopropylmethyldiethoxysilane-tetramethoxysilane copolymers, 3-aminopropylmethyldiethoxysilane-tetraethoxysilane copolymers, and other copolymers containing amino groups, etc.
[0105] In one embodiment of the present invention, the silane coupling agent preferably has a group containing active hydrogen. Specifically, it is more preferable to have at least one functional group selected from amino (primary and secondary), hydroxyl, and mercapto groups, further preferably a primary or secondary amino group, and even more preferably a compound containing Si element having said at least one functional group and at least one alkoxysilyl or silanol group. Amino (primary and secondary), hydroxyl, and mercapto groups are polar; by appropriately selecting these functional groups, the adhesion between the resulting alignment film and polarization film can be controlled, and the bending resistance of the polarization element can be improved. From this viewpoint, the silane coupling agent is preferably a silane coupling agent having an alkoxysilyl group and said at least one functional group. It should be noted that, in order to control the reactivity of the silane coupling agent, the functional group may appropriately have substituents or protecting groups. Examples of silane coupling agents with protecting groups include KBE-9103P (ketimine type) and X-12-1172ES (aldehyde imine type) manufactured by Shin-Etsu Chemical Co., Ltd., for the amino-protected type, and X-12-1056ES for the thiol-protected type.
[0106] Commercially available compounds can also be used as compound (A-2). Examples of such commercially available compounds include KP321, KP323, KP324, KP326, KP340, KP341, X22-161A, KF6001, KBM-1003, KBE-1003, KBM-303, KBM-402, KBM-403, KBE-402, KBE-403, KBM-1403, KBM-502, KBM-503, KBE-502, and KBE-503. Silane coupling agents manufactured by Shin-Etsu Chemical Industry Co., Ltd., such as KBM-5103, KBM-602, KBM-603, KBM-903, KBE-903, KBE-9103, KBM-573, KBM-575, KBM-9659, KBE-585, KBM-802, KBM-803, KBE-846, KBE-9007, X-12-1172ES, X-12-1154, and KR-519.
[0107] The content of compound (A-2) in the composition for forming the alignment film can be appropriately determined according to the type of compound (A-2), the type of substrate, the surface state, the composition of the polarizing film, etc. In one embodiment of the present invention, the content of compound (A-2) relative to 100 parts by mass of the alignment polymer (A-1) is preferably 1 part by mass or more and 30 parts by mass or less, more preferably 2.5 parts by mass or more and 25 parts by mass or less, even more preferably 5.0 parts by mass or more, and even more preferably 23 parts by mass or less. If the content of compound (A-2) is within the above range, it is easy to further improve the bending resistance while maintaining good optical properties, and even when the bending diameter is small, it is expected to suppress the peeling of the alignment film from the substrate and / or the polarizing film.
[0108] Compositions for forming photo-alignment films typically contain solvents. There are no particular limitations on the solvent, as long as it can dissolve the components contained in the composition for forming photo-alignment films. Examples include water; alcohol solvents such as methanol, ethanol, ethylene glycol, isopropanol, propylene glycol, methyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, methyl pentyl ketone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; and chlorinated hydrocarbon solvents such as chloroform and chlorobenzene. These solvents can be used alone or in combination of two or more.
[0109] In this invention, the composition for forming the alignment film may include optional components in addition to the components described above, within a range that does not significantly impair the properties of the alignment film. Examples of such components include polymeric materials and photosensitizers.
[0110] The composition for forming an orientation film can be prepared, for example, by dissolving an orientation polymer (A-1) [or an oligomer or monomer capable of forming the orientation polymer (A-1)], a compound (A-2), and other components as needed in a solvent. For example, the composition for forming an orientation film can be cured as a cured product by curing the composition according to the method described below.
[0111] The thickness of the alignment film is typically in the range of 10 nm or more and 10,000 nm or less, preferably 10 nm or more and 2,500 nm or less, more preferably 10 nm or more and 1,000 nm or less, even more preferably 10 nm or more and 500 nm or less, and particularly preferably 20 nm or more and 250 nm or less. The thickness of the alignment film can be measured using a laser microscope, a film thickness gauge, etc., and the thickness of each layer forming the polarization element, such as the substrate and the polarization film, is measured in the same way.
[0112] <Substrate>
[0113] As the substrate for forming the polarizing element of the present invention, resin films and the like, conventionally known in the field of optical films, can be used. Examples of resins forming the substrate include, for instance, polyolefin resins such as polyethylene and polypropylene; cyclic olefin resins such as norbornene polymers; polyester resins such as polyethylene terephthalate and polyethylene naphthalate; poly(meth)acrylic acid and poly(meth)acrylate resins such as methyl methacrylate; cellulose ester resins such as triacetyl cellulose, diacetyl cellulose, and cellulose acetate propionate; vinyl alcohol resins such as polyvinyl alcohol and polyvinyl acetate; polycarbonate resins; polystyrene resins; polyaryl ester resins; polysulfone resins; polyethersulfone resins; polyamide resins; polyimide resins; polyetherketone resins; polyphenylene sulfide resins; polyphenylene ether resins; and mixtures thereof. From the viewpoints of improved bending resistance, versatility, and heat resistance, at least one resin selected from vinyl alcohol resins, cellulose ester resins, cyclic olefin resins, and poly(meth)acrylic acid resins is preferred.
[0114] In this invention, the substrate preferably has polar groups. Here, "the substrate having polar groups" in this specification means that the substrate has polar groups in its state before the alignment film is formed. Examples of polar groups include hydroxyl, carboxyl, and amino groups. From the viewpoint that the substrate is a material for forming the substrate, can be easily introduced to the surface of the substrate by means of surface modification treatment, and has good reactivity with the active hydrogen reactive groups of the compound (A-2), it is preferable to have at least one polar group selected from hydroxyl, carboxyl, and amino groups, and more preferably hydroxyl groups. By having the substrate with the polar groups before the alignment film is formed, bonds are generated from the reaction between the polar groups present in the substrate and the active hydrogen reactive groups of the compound (A-2) that forms the alignment film, improving the adhesion between the substrate and the alignment film, thereby imparting high bending resistance to the resulting polarization element. Therefore, in one embodiment of the present invention, a bond (e.g., Si-O bond) arising from the reaction between a polar group (present in the substrate) and an active hydrogen reactive group (present in compound (A-2)) can exist between the substrate forming the polarization element of the present invention and the alignment film.
[0115] Preferably, polar groups are present on the surface of the substrate on one side of the laminated oriented film. Such a substrate can be, for example, a substrate obtained by using resins with polar groups, such as vinyl alcohol resins or cellulose resins, as materials and forming them into a film. Alternatively, it can be a substrate obtained by forming a film (precursor film) from a material with polar precursor groups and then modifying the precursor groups in the precursor film to polar groups. Examples of such modification methods include plasma treatment under vacuum or atmospheric pressure, corona treatment, laser treatment, ozone treatment, saponification treatment, or flame treatment. Furthermore, it can also be a substrate in which a polymer with polar groups is attached to the surface of a substrate containing materials without polar groups or their precursor groups, or a substrate in which a polymer with polar precursor groups is attached and then modified to polar groups. Additionally, it can be a substrate obtained by graft polymerization after attaching monomers or polymers with polar groups to the surface of a substrate containing materials without polar groups or their precursor groups, followed by irradiation with radiation, plasma, ultraviolet light, etc. As a method for attaching polymers or monomers having polar groups or precursor groups to the surface of a substrate, for example, a method of coating a solution containing the polymer or monomer onto the surface of the substrate.
[0116] Regarding the thickness of the substrate, from the viewpoints of processability and thin-film polarization elements, it is preferably 1 μm or more and 20 μm or less, and more preferably 1 μm or more and 10 μm or less.
[0117] <Polarizing film>
[0118] In this invention, the polarizing film is a film (layer) with polarizing function. From the viewpoint of achieving ultra-thinness while ensuring bendability suitable for flexible display materials, the polarizing film in the polarizing element of this invention is preferably a coating layer, and more preferably a polarizing film formed by curing a polarizing film forming composition comprising a polymeric liquid crystal compound (B-1), a compound having active hydrogen reactive groups (B-2), and a dichroic pigment (B-3).
[0119] The polymeric liquid crystal compound (B-1) contained in the polarization film forming composition is a compound having at least one polymeric group. Here, a polymeric group refers to a group that can participate in a polymerization reaction due to an active free radical, acid, or the like generated by a polymerization initiator. Examples of polymeric groups in the polymeric liquid crystal compound (B-1) include vinyl, ethyleneoxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, (meth)acryloyl, epoxyethyl, and oxetane. Among these, free radical polymeric groups are preferred, (meth)acryloyl, vinyl, and ethyleneoxy are more preferred, and (meth)acryloyl is even more preferred. If the polymeric liquid crystal compound forming the polarization film has the same functional group (polymeric group) as the compound forming the alignment film, such as (meth)acryloyl, the affinity between the alignment film and the polarization film is increased, and the resulting polarization element can be endowed with excellent bending resistance.
[0120] In this invention, the polymerizable liquid crystal compound (B-1) is preferably a liquid crystal compound exhibiting smectic liquid crystal properties. By using a polymerizable liquid crystal compound exhibiting smectic liquid crystal properties, a polarizing film with high orientation order can be formed. From the viewpoint of achieving higher orientation order, the liquid crystal state exhibited by the polymerizable liquid crystal compound (B-1) is more preferably a higher-order smectic phase (higher-order smectic liquid crystal state). Here, the term "higher-order smectic phase" refers to smectic phases B, D, E, F, G, H, I, J, K, and L, among which smectic phases B, F, and I are more preferred. Liquid crystal properties can be thermotropic or lyotropic; however, from the perspective of achieving dense film thickness control, thermotropic liquid crystals are preferred. Furthermore, the polymerizable liquid crystal compound (B-1) can be a monomer, an oligomer formed by polymerization of polymeric groups, or a polymer.
[0121] As for the polymerizable liquid crystal compound (B-1), there is no particular limitation as long as it is a liquid crystal compound having at least one polymerizable group, and known polymerizable liquid crystal compounds can be used. Examples of polymerizable liquid crystal compounds include compounds represented by the following formula (B1) (hereinafter sometimes referred to as "polymerizable liquid crystal compound (B1)").
[0122] U1 -V 1 -W 1 -(X 1 -Y 1 ) n -X 2 -W 2 -V 2 -U 2 (B1)
[0123] In formula (B1),
[0124] X 1 and X 2 Each of these groups independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group. Here, the hydrogen atom in the divalent aromatic group or divalent alicyclic hydrocarbon group can be substituted by a halogen atom, an alkyl group with 1 to 4 carbon atoms, a fluoroalkyl group with 1 to 4 carbon atoms, an alkoxy group with 1 to 4 carbon atoms, a cyano group, or a nitro group. The carbon atom forming the divalent aromatic group or divalent alicyclic hydrocarbon group can be substituted by an oxygen atom, a sulfur atom, or a nitrogen atom. Wherein, X 1 and X 2 At least one of them is 1,4-phenylene, which may have substituents, or cyclohexane-1,4-diyl, which may have substituents.
[0125] Y 1 It is a single bond or a divalent linker.
[0126] When n is 1 to 3, and n is 2 or more, there are multiple X's. 1 They can be the same or different. X 2 Can be used with multiple X 1 Any or all of them can be the same, or they can be different. Furthermore, when n is 2 or more, multiple Ys... 1 They can be the same or different. From the viewpoint of liquid crystal properties, n is preferably 2 or more.
[0127] U 1 It represents a hydrogen atom or a polymeric group.
[0128] U 2 It indicates a polymerizable group.
[0129] W 1 and W 2 Connecting groups that represent single bonds or divalent bonds independently of each other.
[0130] V 1 and V 2 These can be independently represented as alkyldiyl groups with 1 to 20 carbon atoms that may have substituents, wherein the -CH2- group forming the alkyldiyl group can be replaced by -O-, -CO-, -S-, or NH-.
[0131] In polymeric liquid crystal compounds (B1), X 1 and X 2 The preferred alternatives are 1,4-phenylene, which may have substituents, or cyclohexane-1,4-diyl, which may have substituents, X. 1 and X 2 At least one of them is a 1,4-phenylene that may have a substituent, or a cyclohexane-1,4-diyl that may have a substituent, preferably trans-cyclohexane-1,4-diyl. Examples of substituents optionally present in the 1,4-phenylene or cyclohexane-1,4-diyl group include alkyl groups having 1 to 4 carbon atoms such as methyl, ethyl, and butyl, cyano groups, and halogen atoms such as chlorine and fluorine atoms. Unsubstituted is preferred.
[0132] Furthermore, for the polymerizable liquid crystal compound (B-1), from the viewpoint of easily exhibiting smectic liquid crystal properties, it is preferable that the portion shown in formula (B1') [hereinafter also referred to as the partial structure (B1')] in formula (B1) is an asymmetric structure:
[0133] -(X 1 -Y 1 ) n -X 2 - (B1')
[0134] [In the formula, X] 1 Y 1 X 2 And n each have the same meaning as above.
[0135] As a polymeric liquid crystal compound (B1) in which part of the structure (B1') is asymmetric, examples include n=1 and 1 X. 1 With X 2 These are polymeric liquid crystal compounds (B1) with different structures from each other. Additionally, examples can be given where n is 2, or 2 Y atoms. 1 For the same structure, 2 X 1 For the same structure, 1 X 2 To be with these two X 1 Polymerizable liquid crystal compounds with different structures (B1); 2 X 1 In and W 1 bonded X 1 For X with the other party 1 and X 2 Different structures, the other party's X 1 With X 2 These are polymeric liquid crystal compounds (B1) with identical structures. Furthermore, examples include n=3 and 3 Y atoms. 1 For the same structure, 3 X 1and 1 X 2 Any one of them is a polymeric liquid crystal compound (B1) with a structure different from all three others.
[0136] Y 1 Preferred bonds include -CH2CH2-, -CH2O-, -CH2CH2O-, -COO-, -OCOO-, single bonds, -N=N-, and -CR. a =CR b -、-C≡C-、-CR a =N- or -CO-NR a -. R a and R b Each of the following groups can be independently represented as an alkyl group having 1 to 4 hydrogen atoms or carbon atoms. Y 1 More preferably, it is -CH2CH2-, -COO-, or a single bond, in the presence of multiple Y 1 In the case of X 2 Bonded Y 1 More preferably, it is -CH2CH2- or CH2O-. In X 1 and X 2 When all have the same structure, it is preferable to have two or more Ys with different bonding methods. 1 In the presence of multiple Ys with different bonding methods 1 In such cases, an asymmetric structure is formed, thus there is a tendency for it to exhibit smectic liquid crystal properties.
[0137] U 2 It is a polymerizable group. U 1 It can be a hydrogen atom or a polymeric group, preferably a polymeric group. U 1 and U 2 Preferably, all components are polymerizable groups, and more preferably, all are free radical polymerizable groups. Examples of polymerizable groups include those previously exemplified as polymerizable groups present in the polymerizable liquid crystal compound (B-1). 1 The polymeric groups shown are related to U 2 The polymerizable groups shown may be different from each other, but are preferably of the same kind, preferably U. 1 and U 2 At least one of them is (meth)acryloyl, more preferably both are (meth)acryloyl. Furthermore, the polymerizable group can be in a polymerized state or an unpolymerized state, but the unpolymerized state is preferred.
[0138] As V 1 and V 2Examples of alkyldiyl groups shown include methylene, ethylene, propane-1,3-diyl, butane-1,3-diyl, butane-1,4-diyl, pentane-1,5-diyl, hexane-1,6-diyl, heptane-1,7-diyl, octane-1,8-diyl, decane-1,10-diyl, tetradecane-1,14-diyl, and eicosane-1,20-diyl. 1 and V 2 Preferably, it is an alkyldiyl group with 2 to 12 carbon atoms, and more preferably an alkyldiyl group with 6 to 12 carbon atoms.
[0139] Examples of substituents that may be optionally present in the alkyl diester include cyano groups and halogen atoms; however, the alkyl diester is preferably unsubstituted, and more preferably an unsubstituted straight-chain alkyl diester.
[0140] W 1 and W 2 The components are preferably single bonds, -O-, -S-, -COO-, or -OCOO-, and more preferably single bonds or -O-.
[0141] As a structure that readily exhibits smectic liquid crystal properties, a molecular structure with asymmetry in its molecular structure is preferred. Specifically, the polymeric liquid crystal compound (B-1) is more preferably a polymeric liquid crystal compound having partial structures of (Ba) to (Bi) described below and exhibiting smectic liquid crystal properties. From the viewpoint of readily exhibiting higher-order smectic liquid crystal properties, partial structures of (Ba), (Bb), or (Bc) are more preferred. It should be noted that in (Ba) to (Bi) described below, * indicates a bonding end (single bond).
[0142] [Chemistry 6]
[0143]
[0144] Specifically, examples of polymerizable liquid crystal compounds (B-1) include compounds represented by formulas (B1-1) to (B1-25). When the polymerizable liquid crystal compound (B-1) has a cyclohexane-1,4-diyl group, the cyclohexane-1,4-diyl group is preferably the trans form.
[0145] [Chemistry 7]
[0146]
[0147] [Chemistry 8]
[0148]
[0149] [Chemistry 9]
[0150]
[0151] Among them, preferably at least one is selected from the compounds shown in formulas (B1-2), (B1-3), (B1-4), (B1-5), (B1-6), (B1-7), (B1-8), (B1-13), (B1-14), (B1-15), (B1-16), and (B1-17). As the polymerizable liquid crystal compound (B-1), one may be used alone, or two or more may be used in combination.
[0152] Polymerizable liquid crystal compounds (B-1) can be manufactured, for example, by known methods described in Lub et al., Recl.Trav.Chim.Pays-Bas, 115, 321-328 (1996), or Japanese Patent No. 4719156.
[0153] In this invention, the polarization film forming composition may contain polymeric liquid crystal compounds other than polymeric liquid crystal compound (B1). However, from the viewpoint of obtaining a polarization film with high orientation order, the proportion of polymeric liquid crystal compound (B1) to the total mass of all polymeric liquid crystal compounds contained in the polarization film forming composition is preferably 51% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more.
[0154] When the composition for forming a polarizing film contains two or more polymeric liquid crystal compounds, at least one of them may be a polymeric liquid crystal compound (B1), or all of them may be polymeric liquid crystal compounds (B1). By combining multiple polymeric liquid crystal compounds, liquid crystal properties can be temporarily maintained even at temperatures below the liquid crystal-crystal phase transition temperature.
[0155] The content of the polymeric liquid crystal compound (B-1) in the polarization film forming composition is preferably 40 to 99.9% by mass, more preferably 60 to 99% by mass, and even more preferably 70 to 99% by mass, relative to the solid component of the polarization film forming composition. If the content of the polymeric liquid crystal compound (B-1) is within the above range, there is a tendency for the orientation of the polymeric liquid crystal compound to increase. It should be noted that the term "solid component" in the polarization film forming composition refers to the total amount of components after removing volatile components such as solvents from the polarization film forming composition. Hereinafter, when "solid component" is mentioned in this specification, it also refers to the components after removing volatile components such as solvents from the target composition.
[0156] In this invention, the composition for forming a polarizing film preferably includes a compound (B-2) having an active hydrogen reactive group (hereinafter also referred to as "compound (B-2)"). Examples of active hydrogen reactive groups in compound (B-2) can be the same functional groups that can be present in compound (A-2) contained in the orientation film forming composition. From the viewpoint of reactivity with the active hydrogen-containing groups that compound (A-2) can have, compound (B-2) preferably has at least one group selected from epoxy, glycidyl, isocyanate, and alkoxysilyl groups; more preferably, it has an isocyanate or alkoxysilyl group; and even more preferably, it has an isocyanate group.
[0157] The compound (B-2) typically has 1 to 20 active hydrogen reactive groups, preferably 1 to 10. In a more preferred embodiment of the invention, at least two active hydrogen reactive groups are present. When multiple active hydrogen reactive groups are present, these groups may be identical or different.
[0158] Compound (B-2) preferably has a polymerizable group in addition to an active hydrogen reactive group. The polymerizable group can be, for example, a carbon-carbon unsaturated bond such as a carbon-carbon double bond or a carbon-carbon triple bond; specifically, examples include vinyl, ethyleneoxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, (meth)acryloyl, epoxyethyl, and oxetane. In relation to the orientation polymer (A-1), if compound (B-2) has the same functional group (polymerizable group) as the compound, such as (meth)acryloyl, the affinity between the orientation film and the polarization film increases, further improving the bending resistance of the resulting polarization element; therefore, (meth)acryloyl is preferred.
[0159] The number of polymerizable groups in compound (B-2) is usually 1 to 20, preferably 1 to 10.
[0160] In one embodiment of the present invention, the compound (B-2) preferably has at least one group selected from epoxy, glycidyl, isocyanate and alkoxysilyl as an active hydrogen reactive group, preferably includes (meth)acryloyl group as a polymerizable group, and more preferably has one or more isocyanate groups and (meth)acryloyl groups.
[0161] Specific examples of the compound (B-2) include compounds having a (meth)acryloyl group and an epoxy group, such as methacryloyloxyglycidyl ether and acryloyloxyglycidyl ether; compounds having a (meth)acryloyl group and an oxetanyl group, such as oxetane acrylate and oxetane methacrylate; compounds having a (meth)acryloyl group and a lactone group, such as lactone acrylate and lactone methacrylate; compounds having a vinyl group and an oxazoline group, such as vinyloxazoline and isopropenyloxazoline; compounds having a (meth)acryloyl group and an isocyanate group, such as isocyanatomethyl acrylate, isocyanatomethyl methacrylate, 2-isocyanatoethyl acrylate, and 2-isocyanatoethyl methacrylate; and oligomers of compounds having a (meth)acryloyl group and an alkoxysilyl group, such as 3-acryloxypropyltrimethoxysilane and 3-methacryloxypropylmethyldimethoxysilane. Further examples include compounds having a vinyl group, a vinylene group, and an acid anhydride, such as methacrylic anhydride, acrylic anhydride, maleic anhydride, and vinylmaleic anhydride. Among these, methacryloyloxyglycidyl ether, acryloyloxyglycidyl ether, isocyanatomethyl acrylate, isocyanatomethyl methacrylate, vinyloxazoline, 2-isocyanatoethyl acrylate, 2-isocyanatoethyl methacrylate, 3-acryloxypropyltrimethoxysilane, and the aforementioned oligomers are preferred, and isocyanatomethyl acrylate, 2-isocyanatoethyl acrylate, 3-acryloxypropyltrimethoxysilane, and the aforementioned oligomers are particularly preferred.
[0162] A commercially available product may also be used as the compound (B-2). Examples of such commercially available products include Laromer (registered trademark) PR9000 (manufactured by BASF SE), Karenz AOI (registered trademark) (manufactured by Showa Denko K.K.), Karenz BEI (registered trademark) (manufactured by Showa Denko K.K.), Karenz MOI-EG (registered trademark) (manufactured by Showa Denko K.K.), and KBM-5103 (manufactured by Shin-Etsu Chemical Co., Ltd.).
[0163] When the composition for forming a polarizing film contains the compound (B-2), the compound (B-2) may be the same as or different from the compound (A-2) contained in the composition for forming an alignment film.
[0164] The content of compound (B-2) in the polarizing film forming composition is preferably 0.1 parts by mass or more and 12 parts by mass or less, more preferably 0.5 parts by mass or more and 10 parts by mass or less, and even more preferably 1 part by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the polymerizable liquid crystal compound (B-1). When the content of compound (B-2) is within the aforementioned range, the bending resistance of the polarizing element can be easily improved without compromising the orientation of the resulting polarizing film. Compound (B-2) can be used alone or in combination of two or more. When using two or more compounds (B-2), their total content is preferably within the aforementioned range.
[0165] In this invention, the composition for forming the polarizing film typically includes a dichroic pigment (B-3). Here, a dichroic pigment refers to a pigment that has the property that its absorbance along the long axis of the molecule differs from its absorbance along the short axis. There are no particular limitations on the dichroic pigment (B-3) that can be used in this invention, as long as it possesses the aforementioned properties; it can be a dye or a pigment. Furthermore, two or more dyes or pigments can be used in combination, or a combination of dyes and pigments can be used. Additionally, the dichroic pigment can be polymerizable or liquid crystallizable.
[0166] As a dichroic pigment (B-3), it is preferably found to have a maximum absorption wavelength (λ) in the range of 300–700 nm. MAX Examples of such dichroic pigments include acridine pigments, oxazine pigments, anthocyanins, naphthalene pigments, azo pigments, and anthraquinone pigments.
[0167] Examples of azo dyes include monoazo dyes, diazo dyes, triazo dyes, tetraazo dyes and bis(phenyl)azo dyes, with diazo dyes and triazo dyes being preferred. For example, compounds represented by formula (I) (hereinafter also referred to as "compound (I)") can be cited.
[0168] K 1 (-N=NK) 2 ) p -N=NK 3 (I)
[0169] In formula (I), K 1 and K 3 Independently representing phenyl groups that may have substituents, naphthyl groups that may have substituents, phenyl benzoate groups that may have substituents, or monovalent heterocyclic groups that may have substituents. K 2This indicates a p-phenylene group that may have substituents, a naphthalene-1,4-diyl group that may have substituents, a 4,4'-pyromellitic vinyl group that may have substituents, or a divalent heterocyclic group that may have substituents. p represents an integer from 0 to 4. When p is an integer greater than 2, multiple K groups are represented. 2 They can be the same or different. Within the visible absorption range, -N=N- bonds can be replaced with -C=C-, -COO-, -NHCO-, or -N=CH- bonds.
[0170] Examples of monovalent heterocyclic groups include those derived from heterocyclic compounds such as quinoline, thiazole, benzothiazole, thienothiazole, imidazole, benzimidazole, oxazole, and benzoxazole by removing one hydrogen atom. Examples of divalent heterocyclic groups include those derived from said heterocyclic compounds by removing two hydrogen atoms.
[0171] As K 1 and K 3 The phenyl, naphthyl, phenyl benzoate ester group and monovalent heterocyclic group, as well as K 2 The p-phenylene, naphthalene-1,4-diyl, 4,4'-pyrimidine vinylene, and divalent heterocyclic groups may optionally contain substituents, such as alkyl groups with 1 to 20 carbon atoms, alkyl groups with 1 to 20 carbon atoms having polymerizable groups, alkenyl groups with 1 to 4 carbon atoms; alkoxy groups with 1 to 20 carbon atoms such as methoxy, ethoxy, and butoxy; alkoxy groups with 1 to 20 carbon atoms having polymerizable groups; fluoroalkyl groups with 1 to 4 carbon atoms such as trifluoromethyl; cyano; nitro; halogen atoms; substituted or unsubstituted amino groups such as amino, diethylamino, and pyrrolidinyl (substituted amino groups refer to amino groups having one or two alkyl groups with 1 to 6 carbon atoms, amino groups having one or two alkyl groups with 1 to 6 carbon atoms, or amino groups having two substituted alkyl groups bonded together to form an alkyldiyl group with 2 to 8 carbon atoms. Unsubstituted amino groups are -NH2). It should be noted that, as the polymerizable group, examples include (meth)acryloyl group and (meth)acryloyloxy group.
[0172] In compound (I), the compounds shown in any of the following formulas (I-1) to (I-8) are preferred.
[0173] [Chemistry 10]
[0174]
[0175] [In formulas (I-1) to (I-8),
[0176] B 1 ~B 30Independently represented are hydrogen atoms, alkyl groups having 1 to 6 carbon atoms, alkenyl groups having 1 to 6 carbon atoms, alkoxy groups having 1 to 4 carbon atoms, cyano groups, nitro groups, substituted or unsubstituted amino groups (the definitions of substituted and unsubstituted amino groups are as described above), chlorine atoms, or trifluoromethyl groups.
[0177] n1 to n4 represent integers from 0 to 3 independently.
[0178] When n1 is 2 or more, multiple B 2 They can be the same or different.
[0179] When n² is greater than 2, multiple B 6 They can be the same or different.
[0180] When n3 is 2 or more, multiple B 9 They can be the same or different.
[0181] When n4 is 2 or more, multiple B 14 They can be the same or different.
[0182] The preferred anthraquinone pigment is the compound shown in formula (I-9).
[0183] [Chemistry 11]
[0184]
[0185] In formula (I-9),
[0186] R 1 ~R 8 Independently representing hydrogen atoms, -R x -NH2, -NHR x -NR x 2. -SR x Or halogen atoms.
[0187] R x This refers to an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms.
[0188] The preferred oxazone pigment is the compound shown in formula (I-10).
[0189] [Chemistry 12]
[0190]
[0191] In formula (I-10),
[0192] R 9 ~R 15Independently representing hydrogen atoms, -R x -NH2, -NHR x -NR x 2. -SR x Or halogen atoms.
[0193] R x This refers to an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms.
[0194] The preferred acridine dye is the compound shown in formula (I-11).
[0195] [Chemistry 13]
[0196]
[0197] In formula (I-11),
[0198] R 16 ~R 23 Independently representing hydrogen atoms, -R x -NH2, -NHR x -NR x 2. -SR x Or halogen atoms.
[0199] R x This refers to an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms.
[0200] In equations (I-9), (I-10), and (I-11), R is... x Alkyl groups having 1 to 6 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, and hexyl, while aryl groups having 6 to 12 carbon atoms include phenyl, tolyl, xylyl, and naphthyl.
[0201] The preferred anthocyanins are the compounds shown in formula (I-12) and formula (I-13).
[0202] [Chemistry 14]
[0203]
[0204] In formula (I-12),
[0205] D 1 and D 2 The groups represented by any of the formulas (I-12a) to (I-12d) are independently represented.
[0206] [Chemistry 15]
[0207]
[0208] n5 represents an integer from 1 to 3.
[0209] [Chemistry 16]
[0210]
[0211] In formula (I-13),
[0212] D 3 and D 4 The groups represented by any of the formulas (I-13a) to (I-13h) are independently represented.
[0213] [Chemistry 17]
[0214]
[0215] n6 represents an integer from 1 to 3.
[0216] Among these dichroic pigments, azo pigments are suitable for producing polarizing films with excellent polarization properties due to their high linearity. Therefore, in one embodiment of the present invention, the dichroic pigment (B-3) contained in the polarizing film forming composition for forming the polarizing film is preferably an azo pigment.
[0217] In this invention, the weight-average molecular weight of the dichroic pigment (B-3) is typically 300 to 2000, preferably 400 to 1000.
[0218] In one embodiment of the present invention, the dichroic pigment (B-3) contained in the polarization film forming composition is preferably hydrophobic. If the dichroic pigment (B-3) is hydrophobic, the compatibility between the dichroic pigment (B-3) and the polymeric liquid crystal compound (B-1) is improved, and the dichroic pigment (B-3) and the polymeric liquid crystal compound (B-1) form a uniform phase state, thereby obtaining a polarization film with high orientation order. It should be noted that, in the present invention, the term "hydrophobic dichroic pigment" refers to a pigment with a solubility of less than 1 g in 100 g of water at 25°C.
[0219] The content of the dichroic pigment (B-3) in the polarizing film forming composition can be appropriately determined according to the type of dichroic pigment used, etc., and is preferably 0.1 to 50 parts by mass relative to 100 parts by mass of the polymeric liquid crystal compound, more preferably 0.1 to 20 parts by mass, and even more preferably 0.1 to 12 parts by mass. If the content of the dichroic pigment (B-3) is within the above range, the orientation of the polymeric liquid crystal compound is not easily disturbed, and a polarizing film with high orientation order can be obtained.
[0220] In this invention, the polarization film forming composition used to form the polarization film may contain a polymerization initiator. The polymerization initiator is a compound capable of initiating the polymerization reaction of the polymerizable liquid crystal compound (B-1), and photopolymerization initiators are preferred from the viewpoint of being able to initiate the polymerization reaction at lower temperature conditions. Specifically, photopolymerization initiators capable of generating active free radicals or acids through the action of light can be cited, wherein photopolymerization initiators that generate free radicals through the action of light are preferred. Polymerization initiators may be used alone or in combination of two or more.
[0221] As photopolymerization initiators, known photopolymerization initiators can be used, such as self-destructive photopolymerization initiators and hydrogen-abstracting photopolymerization initiators that generate active free radicals.
[0222] As self-destructive photopolymerization initiators, self-destructive compounds such as benzoin, acetophenone, hydroxyacetophenone, α-aminoacetophenone, oxime esters, acylphosphine oxides, and azo compounds can be used. Additionally, as hydrogen-abstraction photopolymerization initiators, hydrogen-abstraction compounds such as benzophenone, benzoin ethers, benzoylacetyl ketals, dibenzocycloheptanone, anthraquinones, xanthones, thioxanthones, haloacetophenones, dialkoxyacetophenones, halodiimidazoles, halotriazines, and triazines can be used.
[0223] Iodonium salts and matte salts can be used as photopolymerization initiators that generate acids.
[0224] From the viewpoint of preventing pigment dissolution, a reaction at low temperature is preferred. From the viewpoint of reaction efficiency at low temperature, a self-destructive photopolymerization initiator is preferred, and acetophenone compounds, hydroxyacetophenone compounds, α-aminoacetophenone compounds, and oxime ester compounds are particularly preferred.
[0225] As photopolymerization initiators, specifically, the following photopolymerization initiators can be cited as examples.
[0226] Benzoin compounds, including benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether;
[0227] Oligomers of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1,2-diphenyl-2,2-dimethoxy-1-ethyl ketone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, 1-hydroxycyclohexylphenyl ketone and 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]-1-propanone, etc., are hydroxyacetophenone compounds;
[0228] α-aminoacetophenone compounds such as 2-methyl-2-morpholino-1-(4-methylthiophenyl)-1-propanone and 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)-1-butanone;
[0229] 1-[4-(phenylthio)]1,2-octanedione 2-(O-benzoyl oxime), 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]acetone 1-(O-acetyl oxime) and other oxime ester compounds;
[0230] Acylphosphine oxide compounds such as 2,4,6-trimethylbenzoyl diphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide;
[0231] Benzophenone, methyl phthalobenzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyl diphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone and 2,4,6-trimethylbenzophenone and other benzophenone compounds;
[0232] Diethoxyacetophenone and other diekoxyacetophenone compounds;
[0233] 2,4-Bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxynaphthyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxystyryl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(5-methylfuran-2-yl)vinyl]-1,3,5 Triazine compounds, such as 2,4-bis(trichloromethyl)-6-[2-(furan-2-yl)vinyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(4-diethylamino-2-methylphenyl)vinyl]-1,3,5-triazine, and 2,4-bis(trichloromethyl)-6-[2-(3,4-dimethoxyphenyl)vinyl]-1,3,5-triazine, etc., can be used as photopolymerization initiators. The photopolymerization initiator can be appropriately selected from the above-mentioned photopolymerization initiators in relation to the polymerizable liquid crystal compound (B-1) and compound (B-2) contained in the polarization film forming composition.
[0234] Alternatively, commercially available photopolymerization initiators can be used. Examples of commercially available polymerization initiators include Irgacure (registered trademark) 907, 184, 651, 819, 250, and 369, 379, 127, 754, OXE01, OXE02, OXE03 (manufactured by BASF); Omnirad BCIM, Esacure 1001M, Esacure KIP160 (manufactured by IDM Resins BV); Seikuol (registered trademark) BZ, Z, and BEE (manufactured by Seiko Chemical Co., Ltd.); kayacure (registered trademark) BP100 and VUI-6992 (manufactured by Dow Chemical Co., Ltd.); Adeka Optomer SP-152, N-1717, N-1919, SP-170, Adeka Arkls NCI-831, and Adeka Arkls. NCI-930 (manufactured by ADEKA Co., Ltd.); TAZ-A and TAZ-PP (manufactured by Siber Hegner Co., Ltd., Japan); and TAZ-104 (manufactured by Sanwa Chemical Co., Ltd.), etc.
[0235] The content of the polymerization initiator in the polarization film forming composition for forming a polarization film is preferably 1 to 10 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound (B-1), more preferably 1 to 8 parts by mass, further preferably 2 to 8 parts by mass, and particularly preferably 4 to 8 parts by mass. If the content of the polymerization initiator is within the above range, the polymerization reaction of the polymerizable liquid crystal compound can be carried out without significantly disrupting its orientation.
[0236] The composition for forming the polarization film may also contain a photosensitizer. By using a photosensitizer, the polymerization reaction of the polymerizable liquid crystal compound (B-1) can be further promoted. Examples of photosensitizers include xanthones, thioxanthones, and other xanthones (e.g., 2,4-diethylthioxanthone, 2-isopropylthioxanthone); anthracene compounds such as anthracene and alkoxy-containing anthracene (e.g., dibutoxyanthracene); phenothiazines; and rubrene. Two or more photosensitizers may be used alone or in combination.
[0237] When the composition for forming the polarization film contains a photosensitizer, its content can be appropriately determined according to the type and amount of the polymerization initiator and the polymeric liquid crystal compound (B-1). It is preferably 0.1 to 30 parts by mass relative to 100 parts by mass of the polymeric liquid crystal compound (B-1), more preferably 0.5 to 10 parts by mass, and even more preferably 0.5 to 8 parts by mass.
[0238] In addition, the polarizing film forming composition may include a leveling agent. The leveling agent functions to adjust the flowability of the polarizing film forming composition and to make the coating obtained by applying the polarizing film forming composition smoother; specifically, surfactants are examples. Preferably, the leveling agent is selected from at least one of a leveling agent mainly composed of a polyacrylate compound and a leveling agent mainly composed of a compound containing fluorine atoms. Leveling agents may be used alone or in combination of two or more.
[0239] Examples of leveling agents that are mainly composed of polyacrylate compounds include “BYK-350”, “BYK-352”, “BYK-353”, “BYK-354”, “BYK-355”, “BYK-358N”, “BYK-361N”, “BYK-380”, “BYK-381” and “BYK-392” (BYK Chemie).
[0240] Examples of leveling agents whose main component is a compound containing fluorine atoms include "Megafac (registered trademark) R-08", "Megafac R-30", "Megafac R-90", "Megafac F-410", "Megafac F-411", "Megafac F-443", "Megafac F-445", "Megafac F-470", "Megafac F-471", "Megafac F-477", "Megafac F-479", "Megafac F-482" and "Megafac F-483" (DIC Corporation); "Surflon (registered trademark) S-381", "Surflon S-382", "Surflon S-383", "Surflon S-393", "Surflon SC-101", "Surflon SC-105", "KH-40" and "SA-100" (AGC SEIMI). CHEMICAL (Co., Ltd.); “E1830”, “E5844” (DAIKIN FINE CHEMICAL Research Institute); “Eftop EF301”, “Eftop EF303”, “Eftop EF351” and “Eftop EF352” (Mitsubishi Materials Electronics & Chemicals Co., Ltd.).
[0241] When the composition for forming the polarizing film contains a leveling agent, the content of the leveling agent is preferably 0.05 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, relative to 100 parts by mass of the polymeric liquid crystal compound (B-1). If the content of the leveling agent is within the above range, it is easier to orient the polymeric liquid crystal compound (B-1) and less likely to produce unevenness, tending to obtain a smoother polarizing film.
[0242] The composition for forming a polarizing film may contain additives other than photosensitizers and leveling agents. Examples of such additives include antioxidants, release agents, stabilizers, colorants such as bluing agents, flame retardants, and lubricants. When the composition for forming a polarizing film contains other additives, the content of these additives is preferably greater than 0% and less than 20% by mass, and more preferably greater than 0% and less than 10% by mass, relative to the solid content of the composition.
[0243] The polarizing film forming composition can be manufactured using conventionally known methods for preparing polarizing film forming compositions. For example, it can be prepared by mixing and stirring a polymerizable liquid crystal compound (B-1), a compound (B-2), a dichroic pigment (B-3), a polymerization initiator used as needed, and the aforementioned additives. Furthermore, generally speaking, since compounds exhibiting smectic liquid crystal properties have high viscosity, from the viewpoint of improving the coatability of the polarizing film forming composition and facilitating polarizing film formation, the viscosity can be adjusted by adding a solvent to the polarizing film forming composition.
[0244] The solvent used in the polarizing film forming composition can be appropriately selected based on the solubility of the polymeric liquid crystal compound (B-1), compound (B-2), and dichroic pigment (B-3) used. Specifically, the same solvents as those previously exemplified as solvents that can be used in the alignment film forming composition can be cited. One solvent may be used alone, or two or more may be used in combination. The solvent content is preferably 100 to 1900 parts by mass relative to 100 parts by mass of the solid content of the polarizing film forming composition, more preferably 150 to 900 parts by mass, and even more preferably 180 to 600 parts by mass.
[0245] For example, a polarizing film can be obtained by curing the composition for forming the polarizing film according to the method described below. For instance, a polymeric liquid crystal compound (B-1), such as polymeric liquid crystal compound (B1), can form a polarizing film by photopolymerization while maintaining the liquid crystal state of the liquid crystal phase, particularly the smectic phase, preferably a higher-order smectic phase. The polarizing film obtained by polymerization while maintaining the smectic liquid crystal state also exhibits the effect of dichroic pigments, and compared to conventional host-guest type polarizing films, i.e., polarizing films formed from the liquid crystal state of a nematic phase, it has the advantage of high polarization performance. Furthermore, compared to polarizing films coated only with dichroic pigments or lyotropic liquid crystals, it also has the advantage of superior strength.
[0246] In this invention, the polarizing film is preferably a polarizer with a high degree of orientation order. A polarizer with a high degree of orientation order can produce Bragg peaks from higher-order structures such as hexagonal phases and crystalline phases in X-ray diffraction measurements. A Bragg peak refers to a peak originating from a periodic structure of molecular orientation. Therefore, the polarizing film forming the polarizing element of this invention preferably displays a Bragg peak in X-ray diffraction measurements. That is, in the polarizing film forming the polarizing element of this invention, it is preferable to orient the polymeric liquid crystal compound (B-1) or its polymer so that the polarizing film displays a Bragg peak in X-ray diffraction measurements; more preferably, a "horizontal orientation" is performed, in which the molecules of the polymeric liquid crystal compound (B-1) are oriented along the direction of light absorption. In this invention, a polarizer with a periodic interval of 3.0 to 6.0 for molecular orientation is preferred. A high degree of orientation order in displaying the Bragg peak can be achieved by controlling the types and amounts of the polymeric liquid crystal compound (B-1), compound (B-2), and dichroic pigment (B-3), as well as the type and amount of the polymerization initiator.
[0247] The thickness of the polarizing film can be appropriately selected according to the display device to which it is applied, preferably 0.1 to 10 μm, more preferably 0.3 to 9 μm, and even more preferably 0.5 to 8 μm. If the thickness of the polarizing film is above or below the lower limit mentioned above, it is easy to prevent the situation where the necessary light absorption cannot be obtained. If it is below the upper limit mentioned above, it is easy to suppress the generation of orientation defects caused by the reduction of the orientation restraint force of the alignment film.
[0248] In one embodiment of the present invention, the polarizing element may include an outer coating on the side of the polarizing film opposite to the alignment film. The outer coating may function, for example, to prevent the diffusion of dichroic pigments and to prevent damage to the polarizing film. The outer coating is not particularly limited as long as it imparts the desired function to the polarizing element; examples include layers formed from resin compositions containing water-soluble polymers and layers formed from curable compositions containing active energy-curable resins. Water-soluble polymers generally have a significantly different polarity from dichroic pigments, thus providing excellent prevention of dichroic pigment diffusion. Furthermore, improved flexural strength is expected due to the formation of bonds with the reactive hydrogen groups of the compound (B-2) contained in the polarizing film forming composition. Therefore, in one embodiment of the present invention, it is preferable that the outer coating is a layer formed from a resin composition containing a water-soluble polymer.
[0249] Examples of water-soluble polymers capable of forming an outer coating include polyacrylamide polymers; polyvinyl alcohol, and ethylene-vinyl alcohol copolymers, (meth)acrylic acid or its anhydride-vinyl alcohol copolymers, etc.; carboxyvinyl polymers; polyvinylpyrrolidone; starches; sodium alginate; or polyethylene oxide polymers. These polymers can be used alone or in combination of two or more.
[0250] When the outer coating is a layer formed of a resin composition containing a water-soluble polymer (hereinafter also referred to as "a resin composition containing a water-soluble polymer"), the content of the water-soluble polymer in the layer is preferably 75% by mass or more, more preferably 80% by mass or more, and even more preferably 85% by mass or more.
[0251] When the outer coating is a layer formed from a resin composition containing a water-soluble polymer, a cross-linking agent can be used to introduce a cross-linking structure to improve the density of the layer. Examples of such cross-linking agents include ionic cross-linking agents such as glyoxylates and water-soluble additives and cross-linking agents such as epoxy cross-linking agents. Furthermore, for the purpose of imparting water resistance, hydrophobic cross-linking agents such as isocyanate-based cross-linking agents, multi-aldecanter cross-linking agents such as glyoxal and glyoxal derivatives, and metal compound cross-linking agents such as zirconium chloride or titanium lactate can be used.
[0252] When using a crosslinking agent, the amount added can be appropriately determined according to the type of crosslinking agent used. For example, relative to 100 parts by weight of water-soluble polymer, it can be 0.1 to 100 parts by weight, preferably 1 to 50 parts by weight, and more preferably 10 to 30 parts by weight. If the content of the crosslinking agent is within the above range, the outer coating becomes dense, which easily improves the masking effect on dichroic pigments (B-3) in the polarizing film.
[0253] Resin compositions containing water-soluble polymers capable of forming an outer coating are typically prepared in the form of a solution in which the water-soluble polymer is dissolved in a solvent. The solvent can be selected based on the water-soluble polymer used; typically, water, alcohol, and miscibles of water and alcohol are examples, with water being preferred.
[0254] The solid content concentration of the resin composition containing the water-soluble polymer, obtained by adding a solvent to the components that form the outer coating, such as the water-soluble polymer and crosslinking agent, is preferably 1 to 50% by mass, more preferably 2 to 30% by mass, and even more preferably 3 to 15% by mass. If the solid content concentration of the resin composition containing the water-soluble polymer is within the above range, the viscosity of the composition becomes lower, and therefore the coatability and workability become better.
[0255] Resin compositions containing water-soluble polymers may include other components such as additives in addition to solvents such as water-soluble polymers, crosslinking agents, and water. Examples of such other components include preservatives and leveling agents. When a resin composition containing a water-soluble polymer includes other components such as additives, the amount of solids in the resin composition is preferably 10% by mass or less, more preferably 5% by mass or less.
[0256] The necessary components, such as water-soluble polymers and crosslinking agents, are dissolved in a solvent, and the resulting resin composition containing the water-soluble polymer is cured, for example, according to the method described below, thereby forming an outer coating.
[0257] The thickness of the outer coating can be appropriately selected based on the material forming the outer coating and the display device to which it is applied. The thickness of the outer coating can be, for example, 0.1 to 5.0 μm, preferably 0.5 to 3.0 μm.
[0258] The polarization element of the present invention can be manufactured, for example, using a method comprising the following steps:
[0259] (1) A process of forming a coating film comprising an orientation polymer (A-1) and a compound (A-2) having active hydrogen reactive groups on a substrate having polar groups, drying the coating film, thereby causing the active hydrogen reactive groups of the compound (A-2) to react with the polar groups of the substrate to form a bond.
[0260] (2) A process of subjecting the dried coating obtained in step (1) to friction treatment or light irradiation to form an orientation film;
[0261] (3) A step of forming a coating film comprising a polymerizable liquid crystal compound (B-1), a compound having active hydrogen reactive groups (B-2), and a dichroic pigment (B-3) on the alignment film obtained in step (2), and drying the coating film; and
[0262] (4) A process of curing the polymeric liquid crystal compound (B-1) and dichroic pigment (B-3) in the dry coating obtained in step (3) in an oriented state to form a polarizing film.
[0263] Hereinafter, this manufacturing method will also be referred to as "the manufacturing method of the polarization element of the present invention".
[0264] In step (1), known methods such as spin coating, extrusion, gravure coating, die coating, bar coating and coating machine coating, and flexographic printing can be used as methods for coating the composition for forming the orientation film onto the substrate.
[0265] The solvent in the coating of the resulting alignment film forming composition is dried, and the active hydrogen reactive groups of compound (A-2) react with the polar groups of the substrate to form bonds from these functional groups. This ensures a higher adhesion between the substrate and the alignment film. Examples of drying methods for removing the solvent from the coating of the alignment film forming composition include natural drying, ventilation drying, heating drying, and vacuum drying. Heating drying is preferred from the viewpoints of promoting the reaction between the active hydrogen reactive groups of compound (A-2) and the polar groups of the substrate, and from the viewpoint of productivity. The heating drying conditions can be appropriately determined based on the composition of the alignment film forming composition, the type of substrate, and the thickness of the alignment film. For example, the heating temperature can be 50–200°C, preferably 100–150°C. The drying time is typically 20 seconds to 10 minutes, preferably 30 seconds to 5 minutes.
[0266] When the alignment film is a friction alignment film, the dried coating of the alignment film forming composition obtained in step (1) is subjected to friction treatment in step (2), thereby obtaining a friction alignment film. As a friction treatment method, for example, a method can be given by contacting the dried coating of the alignment film forming composition obtained in step (1) with a friction roller wound with a friction cloth and rotating.
[0267] When the alignment film is a photoalignment film, the dried coating of the alignment film forming composition obtained in step (1) is subjected to light irradiation in step (2), thereby obtaining a photoalignment film. By selecting the polarization direction of the irradiated polarized light, the direction of the alignment restraint force can be arbitrarily controlled.
[0268] The method of irradiating with polarized light can be either to directly irradiate the dried coating of the alignment film forming composition formed on the substrate, or to irradiate the substrate side with polarized light and allow the polarized light to be transmitted. The polarized light is preferably substantially parallel light. The wavelength of the irradiated polarized light can be a wavelength in the region where the photoreactive groups of the photo-alignment polymer can absorb light energy. Specifically, UV (ultraviolet light) in the wavelength range of 250–400 nm is preferred. Examples of light sources used for this polarized light irradiation include xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, KrF, ArF, and other ultraviolet lasers, with high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps being more preferred. These lamps are preferred because of the high luminous intensity of ultraviolet light at a wavelength of 313 nm. By passing the light from the light source through a suitable polarizer, polarized UV light can be irradiated. Polarizing filters, Glan-Thomson prisms, Glan-Taylor prisms, and wire-grid polarizers can be used as polarizers.
[0269] If the liquid crystal is shielded during rubbing or polarized light irradiation, multiple regions (patterns) with different liquid crystal orientations can be formed.
[0270] As a method for coating the polarizing film forming composition onto the alignment film in step (3), the same method as the method for coating the alignment film forming composition onto the substrate can be cited. By removing the solvent from the resulting polarizing film forming composition coating under the condition that the polymerizable liquid crystal compound (B-1) contained in the coating does not polymerize, a dry coating film can be formed. As a drying method, the same method as the method for drying the coating film of the alignment film forming composition can be cited. Furthermore, if the compound (A-2) in the alignment film forming composition is a compound having a group containing active hydrogen, the solvent in the coating film of the polarizing film forming composition can be dried, and the active hydrogen-containing group of compound (A-2) reacts with the active hydrogen reactive group of compound (B-2) to form bonds from these functional groups. This ensures a higher adhesion between the alignment film and the polarizing film.
[0271] In addition, in order to transform the polymeric liquid crystal compound (B-1) into a liquid phase, the temperature is raised above the temperature at which the polymeric liquid crystal compound (B-1) transforms into a liquid phase, and then cooled to transform the polymeric liquid crystal compound (B-1) into a liquid crystal phase (smectic phase). This phase transformation can be performed after the removal of solvent from the coating film in step (3), or it can be performed simultaneously with the removal of solvent.
[0272] In step (4), while maintaining the liquid crystal state of the polymerizable liquid crystal compound (B-1), the polymerizable liquid crystal compound (B-1) is polymerized, thereby forming a polarizing film in the form of a cured product of the composition for forming a polarizing film. Photopolymerization is preferred as the polymerization method. In photopolymerization, the light used to irradiate the dried coating film can be appropriately selected based on the type of polymerizable liquid crystal compound (B-1) contained in the dried coating film (especially the type of polymeric groups possessed by the polymerizable liquid crystal compound (B-1), the type of polymerization initiator, and their amounts. The same light source as exemplified in the formation of the photo-alignment film can be used as the light source. The irradiation energy is preferably 10 to 5000 mJ / cm² in the wavelength region effective for activating the polymerization initiator. 2 The setting method is more preferably 100–2000 mJ / cm. 2 Preferably, the polymerizable liquid crystal compound (B-1) and the type of polymerization initiator used in the composition for forming the polarizing film are selected in a manner that allows for photopolymerization using ultraviolet light. Furthermore, during polymerization, the polymerization temperature can be controlled by simultaneously cooling the dried coating film using an appropriate cooling mechanism and then irradiating it with light. During photopolymerization, a patterned polarizing film can also be obtained by performing masking, development, or other similar processes.
[0273] Furthermore, the method for manufacturing the polarization element of the present invention may also include a step of forming an outer coating on the polarization film formed in step (4).
[0274] For example, when the outer coating is formed of a resin composition containing a water-soluble polymer, the resin composition containing a water-soluble polymer is coated on the side of the polarizing film opposite to the orientation film, and the solvent in the coating is dried, removed, and cured, thereby obtaining the outer coating.
[0275] There are no particular limitations on the method of coating a resin composition containing a water-soluble polymer; examples include methods similar to those for coating compositions for forming oriented films.
[0276] The drying temperature and time for forming an outer coating from a resin composition containing a water-soluble polymer are not particularly limited, and can be appropriately determined based on the composition of the resin composition containing the water-soluble polymer. Drying can be performed, for example, by blowing hot air, at a temperature typically between 40 and 100°C, preferably within the range of 60 to 100°C. The drying time is typically between 10 and 600 seconds.
[0277] The polarization element of the present invention can achieve high bending resistance while easily adapting to ultra-thin structures. For example, the total thickness of the polarization element formed from the substrate, the alignment film and the polarization film can be 1.0 to 10.0 μm.
[0278] The polarization element of the present invention can be used in a wide variety of display devices.
[0279] A display device is a device that has display elements, including light-emitting elements or light-emitting devices as light sources. Examples of display devices include liquid crystal displays, organic electroluminescent (EL) displays, inorganic electroluminescent (EL) displays, touch panel displays, electron emission displays (e.g., field emission displays (FEDs), surface electric field emission displays (SEDs)), electronic paper (display devices using electronic inks, electrophoretic elements, plasma displays), projection displays (e.g., grating light valve (GLV) displays, displays with digital micromirror devices (DMDs)), and piezoelectric ceramic displays. Liquid crystal displays can include any type of display, such as transmissive liquid crystal displays, transflective liquid crystal displays, reflective liquid crystal displays, direct-viewing liquid crystal displays, and projection liquid crystal displays. These displays can be two-dimensional or three-dimensional. In particular, the polarization element of this invention is suitable for use in organic electroluminescent (EL) displays and inorganic electroluminescent (EL) displays, as well as in liquid crystal displays and touch panel displays.
[0280] Furthermore, since the polarization element of the present invention can be suitably used in flat panel display devices while possessing high bending resistance and being able to accommodate ultra-thin configurations, it is also suitable as a flexible display material. The flexible display material of the present invention can be suitably incorporated into flexible image display devices.
[0281] Example
[0282] The present invention will now be described in more detail based on embodiments and comparative examples; however, the present invention is not limited to the following embodiments. Unless otherwise specified, "%" and "parts" in the examples refer to mass percentage and mass parts, respectively.
[0283] 1. Example 1
[0284] (1) Preparation of compositions for photo-alignment film formation
[0285] Synthesis Example 1: Synthesis of Oriented Polymer 1
[0286] Oriented polymer 1 contains the following structural units.
[0287] [Oriented Polymer 1]
[0288] [Chemistry 18]
[0289]
[0290] [Synthesis scheme of orientation polymer 1]
[0291] [Chemistry 19]
[0292]
[0293] Synthesis of compound (a1-1-1)
[0294] 50 g (258 mmol) of ferulic acid was dissolved in 360 g of methanol. 10 g of sulfuric acid was added to the resulting solution at room temperature, and the mixture was heated until reflux occurred, then reacted under reflux for 2 hours. The resulting reaction solution was cooled, and 150 g of ice and 150 g of water were added. The supernatant was removed by decantation, and then 150 g of water at 5°C was added to induce crystallization. The resulting white crystals were filtered. The filtered white crystals were washed with 1 M sodium bicarbonate aqueous solution and water, and then dried under vacuum to give 22.2 g of compound (a1-1-1). The yield was 83% based on ferulic acid.
[0295] Synthesis of compound (b1-1-1)
[0296] 25 g (120 mmol) of compound (a1-1-1) was dissolved in 250 g of dimethylacetamide. 33.19 g (240 mmol) of potassium carbonate and 1.99 g (12 mmol) of potassium iodide were added to the resulting solution. 6-Chlorohexanol was added dropwise to the resulting dispersion, and the mixture was stirred at room temperature for 1 hour, then stirred at 70°C for 8 hours. The resulting reaction solution was filtered to remove insoluble matter. 200 g of methyl isobutyl ketone and 300 g of water were added to the filtrate, and the mixture was stirred, allowed to stand, and the organic layer was recovered after separation. 200 g of water was added to the recovered organic layer, and the mixture was stirred, allowed to stand, and separated. This series of water washing operations was repeated twice. The solvent was removed from the recovered organic layer by vacuum distillation using an evaporator to obtain the crude product of compound (b1-1-1).
[0297] Synthesis of compound (c1-1-1)
[0298] The crude product of compound (b1-1-1) was dissolved in 185 g of ethanol. 92 g of water and 14.41 g (360 mmol) of sodium hydroxide were added to the resulting solution, and the mixture was stirred at 80 °C for 1 hour. The reaction solution was cooled to approximately 3 °C, and while maintaining the temperature below 5 °C, 2 M hydrochloric acid was added to adjust the pH to 2. The white precipitate obtained by acid precipitation was collected by filtration, washed twice with a mixture of 100 g of water and 80 g of methanol, and then dried under vacuum to obtain 30.4 g of compound (c1-1-1). The yield was 86% based on compound (a1-1-1).
[0299] Synthesis of compound (M1-1-1)
[0300] 27.46 g (93 mmol) of compound (c1-1-1) was dissolved in 280 g of chloroform. 2.06 g of BHT (di-tert-butyl-hydroxytoluene) and 37.73 g (373 mmol) of triethylamine were added to the resulting solution as polymerization inhibitors, and the mixture was stirred in an ice bath. 29.26 g (260 mmol) of methacrylamide chloride was added dropwise to the reaction solution, and the mixture was stirred for 5 hours at a temperature below 5°C. 5.7 g of dimethylaminopyridine and 190 g of water were added to the resulting reaction solution, and the mixture was stirred for 12 hours at room temperature. After standing, the organic layer was recovered, and 100 g of 2N hydrochloric acid aqueous solution was added to the organic layer. The mixture was stirred, allowed to stand, and separated. This series of washing operations was repeated twice. The organic layer was recovered, and 300 g of n-heptane was added, followed by filtration to collect the precipitated crystals. The compound (M1-1-1) was washed twice with a mixed solvent containing 100 g of water and 80 g of methanol, and then dried under vacuum to obtain 22.0 g of compound (M1-1-1). The yield was 65% based on compound (M1-1-1).
[0301] Synthesis of Oriented Polymer 1
[0302] 1.00 g (2.76 mmol) of compound (M1-1-1) and 10 g of tetrahydrofuran were added to a Schlenk tube. After deoxygenation, 2.27 mg of azobisisobutyronitrile (AIBN) was added while passing nitrogen gas through the tube, and the mixture was stirred at 60 °C for 72 hours. The resulting reaction solution was added to 200 g of toluene. The precipitate was collected by filtration, washed with heptane, and dried under vacuum to obtain 0.75 g of oriented polymer 1. The yield was 75% based on compound (M1-1-1). According to GPC analysis, the molecular weight of the obtained oriented polymer 1 showed a number average molecular weight of 28,200, a weight average molecular weight of approximately 51,300, a Mw / Mn ratio of 1.82, and a monomer content of 0.5%.
[0303] Synthesis Examples 2 and 3: Synthesis of Oriented Polymer 2 and Oriented Polymer 3
[0304] Using the method described in Macromolecules, Vol. 39, No. 26, 9357 (2006), oriented polymers 2 and 3 with the following structures were synthesized. It should be noted that the values in parentheses in the following structural formulas represent the mole fraction of each structural unit relative to the total number of structural units in oriented polymers 2 and 3.
[0305] [Chemistry 20]
[0306]
[0307] [Chemistry 21]
[0308]
[0309] The weight-average molecular weight of oriented polymer 2 is approximately 100,000, and the weight-average molecular weight of oriented polymer 3 is approximately 90,000.
[0310] Synthesis Example 4: Synthesis of Oriented Polymer 4
[0311] Following the synthesis methods of the orientation polymers 2 and 3 described above, an orientation polymer 4 with the following structure was synthesized. It should be noted that the values in parentheses in the following structural formulas represent the mole fraction of each structural unit relative to all structural units of the orientation polymer 4.
[0312] [Chemistry 22]
[0313]
[0314] The weight-average molecular weight of oriented polymer 4 is approximately 95,000.
[0315] Preparation of compositions for photo-aligned film formation
[0316] Two parts of the orientation polymer (orientation polymer 1) prepared by the above operation were mixed with 98 parts of o-xylene, and the mixture was stirred at 80°C for 1 hour to obtain orientation polymer solution 1. Then, 1.0 part of 3-aminopropyltriethoxysilane (trade name: KBE-903, manufactured by Shin-Etsu Chemical Co., Ltd.) was added to the obtained orientation polymer solution 1 as compound (A-2) relative to 100 parts of orientation polymer and mixed to obtain a composition for photo-alignment film formation.
[0317] (2) Preparation of the composition for polarizing film formation
[0318] The following components were mixed and stirred at 80°C for 1 hour to obtain a composition for forming a polarizing film. The polymerizable liquid crystal compound and azo dye described in the examples of Japanese Patent Application Publication No. 2013-101328 were used as the polymerizable liquid crystal compound and the dichroic dye.
[0319] 75 parts of the polymeric liquid crystal compound shown in formula (A-6)
[0320] [Chemistry 23]
[0321]
[0322] 25 parts of the polymeric liquid crystal compound shown in formula (A-7)
[0323] [Chemistry 24]
[0324]
[0325] • 2.8 parts of the dichroic pigment (1) shown below
[0326] [Chemistry 25]
[0327]
[0328] • 2.8 parts of the dichroic pigment (2) shown below
[0329] [Chemistry 26]
[0330]
[0331] • 2.8 parts of the dichroic pigment (3) shown below
[0332] [Chemistry 27]
[0333]
[0334] • Polymerization initiator: 6 parts of 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)-1-butanone (Irgacure 369; manufactured by Ciba Specialty Chemicals).
[0335] Leveling agent: 1.2 parts of polyacrylate compound (BYK-361N; manufactured by BYK-Chemie).
[0336] • Compound (B-2): Two parts of a compound having the following structure (trade name: Laromer (registered trademark) LR-9000, manufactured by BASF).
[0337] [Chemistry 28]
[0338]
[0339] Solvent: 250 parts of cyclopentanone
[0340] (3) Fabrication of acrylic resin films
[0341] An acrylic resin film was prepared based on the description in Japanese Patent Application Publication No. 2020-56835. A composition for forming an acrylic resin layer was obtained by mixing 90 parts of a multifunctional acrylate monomer (ethylene oxide-modified (12-membered) dipentaerythritol hexaacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., "NK Ester A-DPH-12E"), 10 parts of a urethane acrylate polymer (urethane acrylate (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., "Shiguang UV-3310B"), 3 parts of a free radical polymerization initiator (phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide (manufactured by BASF, "Irgacure 819")), and 10 parts of a solvent (methyl ethyl ketone). The mixture was stirred at 50°C for 4 hours.
[0342] After corona treatment of the release surface of the polyethylene terephthalate film (LINTEC SP-PLR382050) (release film) that has undergone release treatment, the above-mentioned acrylic resin layer forming composition is applied using a rod coating method (#2 30mm / sec). The film layer of the resin layer forming composition is then irradiated with an exposure dose of 500mJ / cm using a UV irradiation device (SPOT CURE SP-7; USHIO Electric Co., Ltd.). 2 Ultraviolet light (365nm reference) was used to obtain an acrylic resin film with an acrylic resin layer formed on the surface of the release film. The thickness of the acrylic resin layer was 1.5μm.
[0343] (4) Fabrication of polarization elements
[0344] As a substrate, the acrylic resin film prepared using the above operations was cut into quadrilaterals (10cm x 10cm). To introduce polar groups onto the substrate surface, a corona treatment device (AGF-B10; manufactured by Kasuga Electric Co., Ltd.) was used for one treatment at an output power of 0.3kW and a processing speed of 3m / min. On the corona-treated surface, the composition for forming the photo-aligned film was coated using a bar coater, dried at 80°C for 1 minute, and then irradiated with a polarized UV irradiation device (SPOT CURE SP-7 with a polarizer unit; manufactured by USHIO Electric Co., Ltd.) at 100mJ / cm². 2 The cumulative light intensity was used to perform polarized UV exposure to form an optical alignment film. The thickness of the resulting optical alignment film was measured using an M-220 ellipsometer (manufactured by Japan Spectrophotometer Co., Ltd.), and the result was 40 nm.
[0345] After applying the polarizing film forming composition to the obtained optically aligned film using a bar coater, it is dried in a drying oven set at 120°C for 1 minute.
[0346] Subsequently, a high-pressure mercury lamp (UNICURE VB-15201BY-A, manufactured by USHIO Electric Co., Ltd.) was used to irradiate the area with ultraviolet light (under a nitrogen atmosphere, wavelength: 365nm, cumulative light intensity at wavelength 365nm: 1000mJ / cm²). 2 Thus, a polarizing film is formed in which the polymeric liquid crystal compound and dichroic pigment are oriented, resulting in a polarizing element (1) comprising a substrate / optical alignment film / polarizing film. At this time, the thickness of the polarizing film is measured using an ellipsometer, and the result is 2.0 μm.
[0347] (5) Characteristic Evaluation
[0348] [Evaluation of fit]
[0349] The adhesion between the optical alignment film of the obtained polarizing element (1) and the substrate was evaluated using the following method.
[0350] (Cross-cut test)
[0351] The adhesion between the photoalignment film and the substrate of the obtained polarizing element (1) was evaluated using the cross-cut test (JIS "checkerboard adhesion test") according to JIS D0202-1988. A checkerboard pattern was created on the substrate-side surface of a 10cm × 10cm polarizing element, with 2mm intervals and a 10 × 10 checkerboard shape, penetrating to both the substrate and the photoalignment film. Adhesive tape (25mm wide, made by NICHIBAN) was then fully adhered to the checkerboard surface. The adhesive tape was then peeled off at a 90° angle relative to this surface.
[0352] The number of chessboard patterns that remained without peeling was determined, and the adhesion was evaluated. It should be noted that for the peeled chessboard patterns, X-ray photoelectron spectroscopy (XPS) was used to confirm that the peeling interface was between the photoalignment film and the substrate. The results are shown in Table 1.
[0353] [Optical property evaluation (determination of polarization degree Py and monomer transmittance Ty)]
[0354] The degree of polarization Py and the single-unit transmittance Ty of the polarizing element were measured as follows. In the wavelength range of 380 nm to 780 nm, a spectrophotometer (Shimadzu Corporation UV-3150) with a support equipped with a polarizer was used, and the transmittance (Ta) along the transmission axis and the transmittance (Tb) along the absorption axis were measured using the double-beam method. A grid with a 50% light cutoff was provided on the reference side of the support. The single-unit transmittance and degree of polarization at each wavelength were calculated using the following equations (Equation 1) and (Equation 2). Visibility correction was then performed using a 2-degree field of view (C light source) according to JIS Z 8701, and the visibility-corrected single-unit transmittance (Ty) and visibility-corrected degree of polarization (Py) were calculated. The results are shown in Table 1.
[0355] Monomer transmittance Ty (%) = (Ta + Tb) / 2 (Equation 1)
[0356] Polarization degree Py(%)=(Ta-Tb) / (Ta+Tb)×100 (Equation 2)
[0357] [Evaluation of flexural strength]
[0358] The flexural resistance was evaluated using the general test method for coatings described in JIS-K-5600-5-1 – flexural resistance (cylindrical mandrel method), as shown below.
[0359] The polarizing element (1) was cut into 25mm × 200mm square pieces. A type II cylindrical mandrel bending resistance tester (manufactured by TP Giken Co., Ltd.) was used. Under conditions of 25°C and 55% RH, the polarizing film surface of the cut polarizing element (1) was wound around a mandrel with a diameter of 2mm (bending radius R = 1mm) and a bending resistance test was conducted. After the test, the polarizing element (1) was visually inspected in a dark room using transmitted light to observe the peeling between the substrate and the alignment film. Complete peeling was marked as "×", partial peeling as "△", and no peeling as "○". The results are shown in Table 1.
[0360] 2. Examples 2-23 and Comparative Example 1
[0361] Except for changing the types and amounts of the orientation polymer (A-1), compound (A-2), and compound (B-2) as described in Table 1, polarization elements were fabricated and evaluated using the same procedures as in Example 1. The results are shown in Table 1.
[0362] In Examples 13 to 18, the following compounds (A-2) and (B-2) were used.
[0363] <Compound (A-2)>
[0364] X-12-1172ES (manufactured by Shin-Etsu Chemical Co., Ltd.):
[0365] [Chemistry 29]
[0366]
[0367] X-12-1154 (manufactured by Shin-Etsu Chemical Co., Ltd.): Organic chain type, containing thiol group.
[0368] KR-519 (manufactured by Shin-Etsu Chemical Co., Ltd.): Silicone oligomer containing thiol groups.
[0369] <Compound (B-2)>
[0370] Karenz A01 (manufactured by Showa Denko Co., Ltd.):
[0371] [Chemistry 30]
[0372]
[0373] Karenz BEI (manufactured by Showa Denko Co., Ltd.):
[0374] [Chemistry 31]
[0375]
[0376] Karenz MOI-EG (manufactured by Showa Denko Co., Ltd.):
[0377] [Chemistry 32]
[0378]
[0379] In Table 1, the amount of compound (A-2) added represents the mass parts of compound (A-2) relative to 100 parts by mass of the oriented polymer (A-1), and the amount of compound (B-2) added represents the mass parts of compound (B-2) relative to 100 parts by mass of the polymeric liquid crystal compound.
[0380] Table 1
[0381]
Claims
1. A polarizing element, formed by sequentially stacking a substrate, an alignment film, and a polarizing film adjacent to each other. The orientation film is an orientation film formed by curing a composition comprising an orientation polymer A-1 and a compound A-2 having active hydrogen reactive groups and active hydrogen-containing groups. The substrate is a substrate having at least one polar group selected from hydroxyl, carboxyl, and amino groups. The polarizing film is a polarizing film formed by curing a composition comprising a polymerizable liquid crystal compound B-1, a compound B-2 having an active hydrogen reactive group, and a dichroic pigment B-3. The active hydrogen reactive groups of A-2 and B-2 each independently include at least one selected from the group consisting of epoxy, glycidyl, oxazoline, carbodiimide, aziridinyl, imide, alkoxysilyl, isocyanate, thioisocyanate, and maleic anhydride. The active hydrogen-containing group of A-2 includes at least one selected from hydroxyl, carboxyl, amino, mercapto, primary amide, secondary amide and hydrazide.
2. The polarization element according to claim 1, wherein, Oriented polymer A-1 is a polymer with photoreactive groups that produce dimerization reactions.
3. The polarization element according to claim 1 or 2, wherein, Oriented polymer A-1 is a (meth)acrylic polymer.
4. The polarization element according to claim 1 or 2, wherein, The weight-average molecular weight of the oriented polymer A-1 is above 10,000 and below 1,000,000.
5. The polarization element according to claim 1 or 2, wherein, Compound A-2 is a silane coupling agent.
6. The polarization element according to claim 1 or 2, wherein, Compound A-2 is a silane coupling agent containing at least one functional group selected from primary amino, secondary amino, hydroxyl and mercapto groups.
7. The polarization element according to claim 1 or 2, wherein, The content of compound A-2 is more than 1 part by mass and less than 30 parts by mass relative to 100 parts by mass of oriented polymer A-1.
8. The polarization element according to claim 1 or 2, wherein, Compound B-2 also has polymerizable groups.
9. The polarization element according to claim 8, wherein, The polymerizable group is (meth)acryloyl.
10. The polarizing element according to claim 1 or 2, wherein, Compound B-2 has one or more isocyanate groups and (meth)acryloyl groups.
11. The polarizing element according to claim 1 or 2, wherein, The content of compound B-2 is 0.1 parts by mass or more and 12 parts by mass or less, relative to 100 parts by mass of polymerizable liquid crystal compound B-1.
12. The polarization element according to claim 1 or 2, wherein, Dichroic pigment B-3 includes the compound represented by formula (I): K 1 (-N=N-K 2 ) p -N=N-K 3 (I) In formula (I), K 1 and K 3 Independently representing phenyl groups optionally having substituents, naphthyl groups optionally having substituents, phenyl benzoate groups optionally having substituents, or monovalent heterocyclic groups optionally having substituents. K 2 This indicates optional substituted p-phenylene, optional substituted naphthalene-1,4-diyl, optional substituted 4,4'-mexidiphenylethylene, or optional substituted divalent heterocyclic group. p represents an integer from 0 to 4. When p is an integer greater than 2, there are multiple K. 2 Choose to make them the same or different from each other, and choose to replace the -N=N- bonds with -C=C-, -COO-, -NHCO-, or -N=CH- bonds in the range of absorption displayed in the visible area.
13. The polarization element according to claim 1 or 2, wherein, Polymerizable liquid crystal compound B-1 is a liquid crystal compound that exhibits smectic liquid crystal properties.
14. The polarizing element according to claim 1 or 2, wherein, The thickness of the substrate is greater than 1 μm and less than 10 μm.
15. The polarizing element according to claim 1 or 2, wherein, An outer coating is included on the side of the polarizing film opposite to the orientation film.
16. A manufacturing method for a polarizing element formed by sequentially stacking a substrate, an alignment film, and a polarizing film adjacent to each other, the manufacturing method comprising: (1) A process of forming a coating film comprising an orientation polymer A-1 and a compound A-2 having an active hydrogen reactive group and an active hydrogen group on a substrate having at least one polar group selected from hydroxyl, carboxyl and amino groups, drying the coating film, thereby causing the active hydrogen reactive group of compound A-2 to react with the polar group of the substrate to form a bond; (2) The process of subjecting the dried coating obtained in step 1 to friction treatment or light irradiation to form an orientation film; (3) A process of forming a coating film containing a polymeric liquid crystal compound B-1, a compound B-2 having an active hydrogen reactive group, and a dichroic pigment B-3 on the alignment film obtained in step 2, and drying the coating film. as well as (4) A process of curing the polymeric liquid crystal compound B-1 and dichroic pigment B-3 in the dried coating obtained in step 3 in an oriented state to form a polarizing film. The active hydrogen reactive groups of A-2 and B-2 each independently include at least one selected from the group consisting of epoxy, glycidyl, oxazoline, carbodiimide, aziridinyl, imide, alkoxysilyl, isocyanate, thioisocyanate, and maleic anhydride. The active hydrogen-containing group of A-2 includes at least one selected from hydroxyl, carboxyl, amino, mercapto, primary amide, secondary amide and hydrazide.
17. The manufacturing method according to claim 16, wherein, It also includes the process of forming an outer coating on the polarizing film formed in process 4.
18. A flat panel display device comprising a polarizing element according to any one of claims 1 to 15.
19. A flexible display material comprising the polarizing element according to any one of claims 1 to 15.
Citation Information
Patent Citations
JP1972019156U
Polarizing film, circularly polarizing plate and their manufacturing method
JP2013101328A
Polarization element, circularly polarizing plate, and method of manufacturing those
JP2017102479A
Polarizing film and method for producing the same
JP2020056835A
Composition for forming liquid crystal cured film and use of same
WO2020218104A1
